Highly enhanced ionomer membrane for high selectivity and strength
By integrating a high volume of microporous polymer structure into the composite membrane, the PEMs in fuel cells enhance selectivity and durability while reducing costs, addressing the trade-offs of thickness, hydrogen permeance, and material expenses in existing technologies.
Patent Information
- Application Number
- JP2024172160
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-06-15
- Filing Date
- 2024-10-01
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2038-06-15
AI Technical Summary
Existing polymer electrolyte membranes (PEMs) in fuel cells face challenges in achieving high selectivity, durability, and low cost, with thinner membranes compromising on selectivity due to increased hydrogen permeance and durability, while thicker membranes are costly and prone to damage.
Incorporating a high volume percent of microporous polymer structure into the composite membrane, maintaining high acid content and thickness below 17 microns, which acts as a barrier to reduce permeance and maintain proton conductance, using a combination of microporous polymeric structure and ion exchange material to enhance durability and reduce material costs.
The composite membrane achieves improved selectivity, durability, and reduced costs by maximizing the microporous polymer structure volume, maintaining proton conductance, and minimizing ionomer content, resulting in a thin, durable, and efficient PEM.
Smart Images

Figure 2024177287000030 
Figure 2024177287000031 
Figure 2024177287000032
Abstract
Description
[Technical field]
[0001] Related Applications This application claims priority to PCT Patent Application No. PCT / US2017 / 037595, entitled HIGHLY REINFORCED IONOMER MEMBRANES FOR HIGH SELECTIVITY AND STRENGTH, filed June 15, 2017, the disclosure of which is incorporated herein in its entirety.
[0002] FIELD OF THEINVENTION The present disclosure relates to polymer electrolyte membranes, and in particular to composite membranes having a high volume percentage of microporous polymer structure and surprisingly high selectivity for proton transport relative to hydrogen transport. [Background technology]
[0003] 2. Background of the Invention Polymer electrolyte membranes (PEMs) are key components in many applications such as fuel cells, electrolyzers, flow batteries, and humidifiers. Of these, polymer electrolyte membrane fuel cells (PEMFCs) are of particular interest. In a PEMFC, the PEM is part of a membrane electrode assembly (MEA). The MEA is the central component of the fuel cell where the electrochemical reaction occurs to generate power. A typical MEA includes a PEM, two catalyst layers (anode and cathode attached to either side of the PEM), and two gas diffusion layers (GDLs attached to the two outer surfaces of the catalyst layers). The PEM separates the two reactant gas streams. At the anode side of the MEA, a fuel, e.g., hydrogen gas, is oxidized and separated into electrons and protons. The cell is designed such that the electrons pass through an external circuit while the protons move through the PEM. At the cathode side, the electrons and protons react with an oxidant (i.e., oxygen or air) to produce water and heat. In this way, the electrochemical potential is maintained and an electric current can be drawn from the fuel cell to perform useful work.
[0004] There are several important properties desired in a PEM for fuel cell applications. As mentioned above, the primary function of a PEM in a PEMFC is to transport protons with minimal resistance while keeping the reactant gases separated. Thus, conductance and permeance are important properties of a PEM. Herein, conductance refers to the transport of protons from the anode side to the cathode side of the MEA. Conductance affects the performance and power density of the fuel cell. Similarly, permeance refers to the transport of hydrogen from the anode side to the cathode side of the MEA. Permeance affects the fuel efficiency of the fuel cell. The ratio of these two properties (i.e., proton conductance divided by hydrogen permeance) is called selectivity. Another important property of a PEM is strength, which affects the useful life of the PEM in an application. The cost of a PEM is also an important consideration, especially in the automotive market, and is the primary economic driver of PEMFC technology.
[0005] High selectivity (due to high conductance and / or low permeance), high durability, and low cost are all desirable qualities in a PEM. However, as a practical engineering problem, there are often conflicts in optimizing these properties, and trade-offs must be accepted. One can attempt to improve selectivity by increasing conductance through a decrease in membrane thickness. Thinner PEMs also reduce cost, since ionomers are expensive and used in smaller quantities. However, as the membrane is made thinner, hydrogen permeation increases, compromising the selectivity gains from increased proton conductance, resulting in thinner membranes being less selective than thicker membranes. Furthermore, thinner membranes are weaker and often lack sufficient mechanical durability for aggressive automotive conditions. Reducing the membrane's physical thickness makes it more susceptible to damage or puncture from other fuel cell components, shortening the cell's lifespan. Another way to improve selectivity is by increasing the acid concentration of the PEM. Typically, increasing the acid concentration improves selectivity by increasing proton conductivity without the need to reduce thickness and without a significant adverse effect on hydrogen permeation. However, as the overall acid content increases, excessive hydration reduces the PEM's durability in harsh automotive conditions. As the overall acid content of the PEM increases, its cost also increases, as low equivalent weight ionomers are typically much more expensive. As these examples show, managing these PEM design tradeoffs can be difficult, especially when optimizing for selectivity, durability, and cost.
[0006] Bahar et al., U.S. Pat. No. 5,599,614, describes an integral composite membrane comprising a base material and an ion exchange material. The base material is a microporous membrane defined by a thickness of less than 1 mil (e.g., 0.8 mil) and a microstructure characterized by nodes interconnected by fibrils or by fibrils in the absence of nodes. The ion exchange resin substantially impregnates the membrane such that the membrane is essentially air impermeable. The resulting composite membrane is characterized by enhanced strength due to the microporous membrane, allowing for a reduction in the thickness of the impregnated layer, thereby lowering the resistance to proton conduction. Thus, these thin integral composite membranes can provide lower resistance while maintaining high strength.
[0007] Hobson et al., U.S. Patent No. 6,613,203, describes a composite membrane comprising an expanded polytetrafluoroethylene (ePTFE) membrane impregnated with an ion exchange material. ePTFE has a morphological structure of highly elongated nodes interconnected by fibrils. The composite membrane exhibits increased stiffness and durability, allowing for a reduction in the thickness of the composite membrane and improved proton conductivity in fuel cells.
[0008] Efforts have been made to produce ion exchange resins with higher acid content to improve fuel cell performance by increasing proton conductance. Wu et al., U.S. Patent No. 8,071,702, demonstrates that low equivalent weight (high acid content) ionomers can be produced with low hydration (i.e., water uptake), which is beneficial for increasing proton conductivity.
[0009] However, the above mentioned techniques still have drawbacks. In particular, the teachings of Bahar et al. and Hobson et al. direct the composite membrane to be thinner so that the fuel cell can benefit from the increased proton conductance. However, Bahar et al. and Hobson et al. do not teach how to improve or keep constant the selectivity of the composite membrane. The problem of reduced selectivity due to the increased hydrogen permeance of thinner membranes was not addressed in their inventions. Also, the problem of the high cost of low equivalent weight ionomers was not addressed. This approach to composite PEM design provides a reasonable trade-off between selectivity, durability and cost and has dominated the automotive PEMFC market for about 20 years. However, recently, the relatively low selectivity of existing composite PEMs has begun to limit further improvement. Thus, there is a need for thin composite membranes that combine high selectivity with high durability and low cost. Summary of the Invention
[0010] Summary of the Invention The inventors of the present invention have endeavored to solve the above-mentioned problems. As a result, they have discovered that selectivity is improved due to the increased crystallinity of the composite PEM, which acts as a barrier to reduce permeance, while maintaining a high acid content, thereby maintaining a desired proton conductance. Furthermore, the composite membrane developed according to the present disclosure advantageously (i) has an increased volume of microporous polymer structure relative to the total volume of the PEM, thus improving durability, and (ii) has a lower material cost due to a lower ionomer content.
[0011] According to one aspect of the present invention, there is provided a composite membrane comprising: (1) a microporous polymer structure present in an amount of 13% to 65% by volume based on the total volume of the composite membrane; and (2) an ion exchange material at least partially embedded within and occluding the microporous polymer structure, the ion exchange material having an equivalent volume of 460 cc / mol equivalent or less. The composite membrane has an acid content of 1.2 meq / cc to 3.5 meq / cc. The thickness of the composite membrane is less than 17 microns. The composite membrane can have a selectivity of greater than 0.05 MPa / mV. In some embodiments, the composite membrane can have a selectivity of greater than 0.35 MPa / mV. In some embodiments, the composite membrane can have a selectivity of greater than 0.50 MPa / mV. In other embodiments, the composite membrane can have a selectivity of greater than 0.80 MPa / mV. The composite membrane can include at least one support layer attached to one or more outer surfaces of the microporous polymer structure.
[0012] In some embodiments, the ion exchange material can be fully embedded within the microporous polymer structure. The ion exchange material can include multiple ion exchange materials in the form of a mixture of ion exchange materials. The mixture of ion exchange materials has an equivalent volume of 460 cc / mole equivalent or less. In other embodiments, the ion exchange material can include multiple layers of ion exchange material. The layers of ion exchange material can be formed from the same ion exchange material. Alternatively, the layers of ion exchange material can be formed from different ion exchange materials. The average equivalent volume of all layers of ion exchange material is 460 cc / mole equivalent or less. At least one of the layers of ion exchange material includes a mixture of ion exchange materials. The ion exchange material can include an ionomer. The at least one ionomer can include a proton conducting polymer. The proton conducting polymer can include a perfluorosulfonic acid. In one embodiment, the at least one ionomer can have a density of 1.96 g / cc or more at 0% relative humidity. In another embodiment, the at least one ionomer can have a density of 1.8 g / cc or more at 0% relative humidity. In yet another embodiment, the at least one ionomer can have a density of 1.0 g / cc or greater at 0% relative humidity.
[0013] In some embodiments, the microporous polymer structure has a first surface and a second surface. The ion exchange material can form a layer on the first surface, on the second surface, or on both the first and second surfaces. According to various embodiments, the ion exchange material can be partially embedded within the microporous polymer structure, leaving a non-occluded portion of the microporous polymer structure closest to the first surface, the second surface, or both. The non-occluded portion may not include any ion exchange material. The non-occluded portion can include a coating of ion exchange material on the inner surface of the microporous polymer structure.
[0014] According to various embodiments, the microporous polymer structure comprises at least two microporous polymer layers. The microporous polymer layers may be the same or the microporous polymer layers may be different. The at least two microporous polymer layers may be in direct contact. In some embodiments, at least two of the microporous polymer layers may not be in direct contact.
[0015] In some embodiments, the microporous polymer structure can include a fluorinated polymer. In some embodiments, the microporous polymer structure can include a perfluorinated porous polymer material. The fluorinated porous polymer material can include polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (ePTFE), polyvinylidene fluoride (PVDF), expanded polyvinylidene fluoride (ePVDF), expanded poly(ethylene-co-tetrafluoroethylene) (eEPTFE), or mixtures thereof. In other embodiments, the microporous polymer structure can include a hydrocarbon polymer. The hydrocarbon material can include polyethylene, polypropylene, polycarbonate, or polystyrene.
[0016] The present invention also includes a membrane electrode assembly, a fuel cell, and a redox flow battery each including the above composite membrane.
[0017] According to the present invention, the volume of the microporous polymer structure is increased relative to the total volume of the composite membrane. This improves the durability of the composite membrane. Furthermore, the ion exchange material maintains its low equivalent weight, which compensates for the dilution of the ionomer caused by the increase in the volume of the microporous polymer structure. Thus, the overall acid content and overall thickness of the composite membrane remain substantially the same. By increasing the volume of the microporous polymer structure while preserving the acid content and overall thickness of the composite membrane, embodiments of the present disclosure can maintain current (or improved) levels of conductance while maintaining an ultra-thin profile and improved durability and permeance characteristics.
[0018] Surprisingly, it has been found that the selectivity of the composite membrane can be improved by maximizing the volume percent of the microporous polymer structure, provided that the total acid concentration in the composite membrane is also maintained at a high level.
[0019] Other aspects and modifications of the present invention will become apparent from the ensuing discussion. [Brief description of the drawings]
[0020] BRIEF DESCRIPTION OF THE DRAWINGS The present disclosure will be better understood in view of the following non-limiting figures.
[0021] [Figure 1A] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 1B] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 1C] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 1D] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 1E] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 1F] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 1G] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention.
[0022] [Figure 2A] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 2B] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 2C] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention.
[0023] [Figure 2D] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 2E]1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention. [Figure 2F] 1 shows a cross-sectional side view of a composite membrane according to some embodiments of the present invention.
[0024] [Figure 3A] 1 shows graphs illustrating certain properties of composite membranes according to some embodiments of the present invention. [Figure 3B] 1 shows graphs illustrating certain properties of composite membranes according to some embodiments of the present invention.
[0025] [Figure 4A] 1 shows an exemplary flow diagram of a method for constructing an exemplary composite membrane, according to some aspects of the present invention. [Figure 4B] 1 shows an exemplary flow diagram of a method for constructing an exemplary composite membrane, according to some aspects of the present invention. [Figure 4C] 1 shows an exemplary flow diagram of a method for constructing an exemplary composite membrane, according to some aspects of the present invention.
[0026] [Figure 5A] 1 shows a diagram of an MEA including a composite membrane according to some embodiments of the present invention.
[0027] [Figure 5B] 1 shows a diagram of a fuel cell including a composite membrane according to some embodiments of the present invention.
[0028] [Figure 6] 1 shows a table illustrating the properties of microporous polymer structures used in various test procedures in a series of examples according to some aspects of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Detailed Description of the Invention It has been discovered that the selectivity of the composite membrane can be surprisingly improved by maximizing the volume percent of the microporous polymer structure, provided that the total acid concentration in the composite membrane is maintained at a high level while the thickness of the composite membrane is kept below a threshold value (e.g., less than 17 microns).
[0030] This improvement is surprising for several reasons. First, ideal impregnation of the microporous polymer structure was expected to have little effect on selectivity, since the microporous polymer structure is a very effective barrier to both proton and hydrogen transport and therefore would not affect their ratio. Second, increasing the volume percent of the microporous polymer structure makes it more difficult to achieve complete blockage. Residual porosity is expected to provide leakage paths that would increase hydrogen permeance and therefore reduce selectivity. Finally, the lack of complete blockage and resulting low selectivity is also expected due to the difficulty in absorbing the low equivalent weight ionomers necessary to maintain high acid concentrations in the composite PEM. This difficulty in absorption is a direct result of the stronger polyelectrolyte effect inherent in solutions of lower equivalent weight ionomers, resulting in increased viscosity that prevents absorption into the small pores of the microporous polymer structure.
[0031] Nevertheless, it has now been shown that selectivity can be improved by fabricating a PEM with a high volume percentage of microporous polymer structure. Without limiting the scope of the claims, the microporous polymer structure acts as a barrier to gas permeance, and as the volume fraction of the microporous polymer structure in the composite PEM increases, selectivity is improved while maintaining desirable proton conductance without increasing the overall thickness of the composite membrane at high acid content.
[0032] Previous efforts to develop composite membranes with high acid content resulted in a reduction in the reinforcement volume fraction of the composite membrane. This, in return, led to increased production costs because more expensive ionomer was used. As a result, thicker membranes were required to prevent failure of such fuel cells. The inventors of the present invention have been able to develop composite membranes with high acid content (e.g., acid content of 1.2 meq / cc to 3.5 meq / cc) while keeping the thickness of the composite membrane below a threshold value (e.g., less than 17 microns). This was achieved by increasing the volume of the microporous polymer structure within the composite membrane while maintaining the acid content and overall thickness of the composite membrane. Surprisingly, the inventors of the present invention have discovered that incorporating a larger volume fraction of the microporous polymer structure while maintaining the acid content leads to improved selectivity because the crystallinity of the composite PEM is increased, which acts as a barrier to reduce permeance, while the acid content is kept high, thereby maintaining the desired proton conductance.
[0033] Furthermore, the composite membranes developed according to the present disclosure advantageously have: (i) an increased volume of the microporous polymer structure relative to the total volume of the PEM, thus improving durability; and (ii) lower material costs due to lower ionomer content. According to various embodiments, a composite membrane with comparable proton conductance but lower permeance when using an ionomer with a higher acid concentration can be achieved by increasing the volume of the microporous polymer structure. That is, the acid concentration of the ionomer and the volume percentage of the microporous polymer structure used in the composite membrane of the present disclosure are higher than the acid concentration of the ionomer and the volume percentage of the microporous polymer structure used in a conventional composite membrane having substantially the same thickness as the composite membrane of the present disclosure. In some embodiments, this results in a composite membrane with increased selectivity when the volume of the microporous polymer structure is increased relative to the total volume of the PEM.
[0034] This aims at a fundamentally different design strategy for a new generation of composite membranes, i.e., thin membranes that provide very highly enhanced, high selectivity. Thus, aspects of the present disclosure relate to increasing the volume of the microporous polymer structure relative to the total volume of the PEM, while surprisingly and unexpectedly maintaining or increasing the PEM selectivity without increasing the thickness of the composite membrane beyond a certain threshold.
[0035] In one embodiment, the present disclosure relates to a composite membrane comprising a microporous polymer structure occupying 13% to 65% by volume of the total volume of the composite membrane, and an ion exchange material (e.g., ionomer) at least partially embedded within the microporous polymer structure. The acid content of the composite membrane is 1.2 meq / cc to 3.5 meq / cc, while the thickness of the composite membrane is maintained below 17 microns. The selectivity of the composite membrane is based on proton conductance and hydrogen permeance, in some cases, greater than 0.05 MPa / mV. Advantageously, by utilizing two distinct materials (i.e., the microporous polymer structure and the ion exchange material), the volume of the microporous polymer structure can be increased relative to the total volume of the composite membrane, resulting in improved durability. Furthermore, the ion exchange material can maintain its low equivalent weight, which compensates for the dilution of the ionomer caused by the increased volume of the microporous polymer structure, thereby preserving the acid content and overall thickness of the composite membrane. By increasing the volume of the microporous polymer structure while maintaining the acid content and overall thickness of the composite membrane, embodiments of the present disclosure can maintain this (or improved) level of conductance while maintaining an ultra-thin profile, improved durability and permeance characteristics.
[0036] The embodiments have been described using volume-based values instead of mass-based values to provide a method of meaningful comparison between composite membranes containing microporous polymer structures and ionomers of different densities. Volume-based normalization has been noted in the scientific literature as being suitable for describing transport phenomena such as proton conduction in PEMs used in fuel cells (e.g., Kim, YS; Pivovar, BS Annu. Rev. Chem. Biomol. Eng. 2010, 1, 123-148). More specifically, although weight-based measurements can be used to make comparisons between polyelectrolytes, there are significant limitations when correlating with proton conductivity. These limitations arise, in part, because the densities of different polymers can be significantly different and because conduction occurs at length scales that are better represented by volume-based measurements rather than mass-based measurements.
[0037] Various definitions used in this disclosure are provided below.
[0038] As used herein, the term "selectivity" refers to the ratio of the proton conductance of a composite membrane divided by the hydrogen permeance of the composite membrane. For fuel cell applications, composite membranes with high selectivity (due to high conductance and / or low permeance) are preferred. The proton conductance of a composite membrane is measured as ionic conductivity per unit thickness. The permeance of a composite membrane can be measured as permeability (e.g., hydrogen permeance) per unit thickness.
[0039] As used herein, the term "permeance" refers to the ability of a composite membrane to transport hydrogen gas, with lower permeance values generally being preferred for a desired fuel efficiency. The term "conductance" refers to the ability of a composite membrane to transport protons, with higher conductance values generally being preferred for a desired power density.
[0040] As used herein, the terms "ionomer" and "ion exchange material" refer to cation exchange materials, anion exchange materials, or ion exchange materials that contain both cation and anion exchange capacity. Mixtures of ion exchange materials can also be used. The ion exchange materials can be perfluorinated or hydrocarbon-based. Suitable ion exchange materials include, for example, perfluorosulfonic acid polymers, perfluorocarboxylic acid polymers, perfluorophosphonic acid polymers, styrene-based ion exchange polymers, fluorostyrene ion exchange polymers, polyaryletherketone ion exchange polymers, polysulfone ion exchange polymers, bis(fluoroalkylsulfonyl)imides, (fluoroalkylsulfonyl)(fluorosulfonyl)imides, polyvinyl alcohol, polyethylene oxide, divinylbenzene, metal salts with or without polymers, and mixtures thereof. In an exemplary embodiment, the ion exchange material comprises a perfluorosulfonic acid (PFSA) polymer made by copolymerization of tetrafluoroethylene and perfluorosulfonyl vinyl ester with conversion to proton form.
[0041] As used herein, the "equivalent weight" of an ionomer or ion exchange material refers to the weight (molecular weight) of polymer in the ionomer per sulfonic acid group. Thus, a lower equivalent weight indicates a higher acid content. The equivalent weight (EW) of an ionomer refers to the EW when the ionomer is in the proton form at 0% RH and impurities are negligible. The term "ion exchange capacity" refers to the reciprocal of the equivalent weight (1 / EW).
[0042] As used herein, the "equivalent volume" of an ionomer or ion exchange material refers to the volume of ionomer per sulfonic acid group. The equivalent volume (EV) of an ionomer refers to the EV when the ionomer is pure, in the proton form at 0% RH, and with negligible impurities.
[0043] As used herein, the term "acid content" or "acid concentration" of a composite membrane refers to the sulfonic acid group content in the composite membrane, and is determined on a volumetric basis, unless otherwise specified herein.
[0044] As used herein, the term "burst strength" refers to the pressure at which a film or sheet of a composite membrane, such as a PEM, will burst. The burst strength of a PEM is highly dependent on the tensile strength and elongation of the materials that make up the PEM.
[0045] As used herein, the term "microporous polymer structure" refers to a polymer matrix that supports the ion exchange material and adds structural integrity and durability to the resulting composite membrane. In some exemplary embodiments, the microporous polymer structure comprises an expanded polytetrafluoroethylene (ePTFE) membrane having a node and fibril structure. In other exemplary embodiments, the microporous polymer structure comprises a track-etched polycarbonate membrane having a smooth flat surface, high apparent density, and well-defined pore size.
[0046] As used herein, the interior volume of a microporous polymer structure is said to be "substantially occluded" when said interior volume has a structure characterized by a low volume void of less than 10% by volume and a high gas impermeability, a Gurley number greater than 10,000 seconds. Conversely, the interior volume of a microporous polymer structure is said to be "unoccluded" when said interior volume has a structure characterized by a higher void volume of more than 10% and a gas permeability, a Gurley number less than 10,000 seconds.
[0047] I. Composite membrane As shown in Figures 1A-1D, a composite membrane 100 is provided that includes a microporous polymer structure 105 and an ion exchange material (e.g., an ionomer) 110 impregnated in the microporous polymer structure 105. That is, the microporous polymer structure 105 is imbibed with the ion exchange material. The ion exchange material 110 can substantially impregnate the microporous polymer structure 105 so as to substantially occlude the internal volume (i.e., the internal volume has a structure characterized by low void volume and high gas impermeability). For example, by filling more than 90% of the internal volume of the microporous polymer structure 105 with the ion exchange material 110, substantial occlusion will occur and the membrane will be characterized by a Gurley number greater than 10,000 seconds. As shown in Figures 1A-1D, the ion exchange material 110 is firmly attached to the inner and outer surfaces of the microporous polymer structure 105, e.g., to the fibrils and / or nodes of the microporous polymer structure forming the absorbent layer 104.
[0048] In some embodiments, the ion exchange material 110 is provided as one or more additional layers 115 (e.g., also referred to as a "butter coat (BC)") on one or more outer surfaces of the absorbent layer 104 in addition to being impregnated into the microporous polymer structure 105 of the absorbent layer 104 (FIGS. 1A-1C). In other embodiments, the ion exchange material 110 is provided only impregnated into the microporous polymer structure 105 within the absorbent layer 104, i.e., without an additional layer (FIG. 1D). Nevertheless, the composite membrane 100 is characterized by a microporous polymer structure 105 that occupies a volume of more than 13% of the total volume of the composite membrane 100, which total volume includes the volume of the additional layer 115, if present.
[0049] In additional embodiments, a portion of the microporous polymer structure 105 (e.g., the upper surface region or the lower surface region) can include a non-occluding (i.e., an interior volume characterized by a high void volume and high gas permeability) layer 112, which is free or substantially free of ion exchange material 110 (FIGS. 1E-1F). The location of the non-occluding layer 112 is not limited to the upper surface region of the microporous polymer structure 105. As described above, the non-occluding layer 112 can be provided on the lower surface region of the microporous polymer structure 105.
[0050] In yet other embodiments, the non-occlusive layer 112 can include a small amount of ion exchange material 110 present as a thin node and fibril coating on the inner surface of the microporous polymer structure 105. However, the amount of ion exchange material 110 does not have to be great enough to cause the microporous polymer structure 105 to become occlusive, thereby forming a non-occlusive layer 112.
[0051] In some embodiments, the composite membrane 100 can be provided on a support layer 114 (FIG. 1G). The support layer 114 can include a backer, e.g., a release film, such as a cycloolefin copolymer (COC) layer. In some embodiments, the composite membrane 100 can be released (or otherwise separated) from the support layer 114 before being incorporated into a membrane electrode assembly (MEA).
[0052] 1A-1G show an exemplary composite membrane 100 that includes a single type of ion exchange material 110. However, applications are not limited to composite membranes 100 having a single type of ion exchange material 110 or a single absorbing layer 104.
[0053] 2A-2C, the composite membrane 200 can also include multiple, e.g., two or more, absorbent layers 104a and 104b. In the embodiment of FIG. 2A, a first absorbent layer 104a can be formed by imbibing an ion exchange material 110 into a microporous polymer structure 105, and a second absorbent layer 104b can be formed by imbibing the same ion exchange material 110 into the microporous polymer structure 105. For example, an ion exchange material can be imbibed onto a first surface of the microporous polymer structure to form the first absorbent layer 104a, and the same ion exchange material can be imbibed onto a second surface of the microporous polymer structure opposite the first surface to form the second absorbent layer 104b. 2B embodiment, the first absorbent layer 104a can be formed by imbibing a first ion exchange material 110a into the microporous polymer structure 105, and the second absorbent layer 104b can be formed by imbibing a second ion exchange material 110b, different from the first ion exchange material 110a, into the microporous polymer structure 105. In this embodiment, the first ion exchange material can be imbibed onto a first side of the microporous polymer structure to form the first absorbent layer 104a, and the second ion exchange material can be imbibed onto a second side of the microporous polymer structure opposite the first side to form the second absorbent layer 104b.
[0054] In some embodiments, one or more ion exchange materials 110, first ion exchange material 110a and / or second ion exchange material 110b, can be provided on one or more outer surfaces of absorbent layers 104a and / or 104b as one or more additional layers 115 (Figures 2A-2C), optionally included between absorbent layers 104a and 104b, as shown in Figure 2C.
[0055] As shown in Figures 2D-2F, the composite membrane 300 can also include multiple, e.g., two or more, absorbent layers 104c and 104d formed by two (or more) different microporous polymer structures 105a and 105b. In some embodiments, the first absorbent layer 104c can be formed by imbibing an ion exchange material 110 into the first microporous polymer structure 105a, and the second absorbent layer 104b can be formed by imbibing the same ion exchange material 110 into the second microporous polymer structure 105b (Figure 2D). In other embodiments, the first absorbent layer 104c can be formed by imbibing a first ion exchange material 110a into the first microporous polymer structure 105a, and the second absorbent layer 104b can be formed by imbibing a second ion exchange material 110b into the second microporous polymer structure 105b. 2D-2F, the first microporous polymer structure 105a can be different from the second microporous polymer structure 105b. The first ion exchange material 110a can be the same as or different from the second ion exchange material 110b.
[0056] In some embodiments, the ion exchange material 110, the first ion exchange material 110a and the second ion exchange material 110b, can be provided as one or more additional layers 115 on one or more outer surfaces of the absorbent layers 104c and 104d such that the first microporous polymer structure 105a is in direct contact with the second microporous polymer structure 105b (FIGS. 2D-2E). In some embodiments, the ion exchange material 110, the first ion exchange material 110a and the second ion exchange material 110b, can be provided as one or more additional layers 115 between the absorbent layers 104c and 104d such that the first microporous polymer structure 105a is not in direct contact with the second microporous polymer structure 105b (FIG. 2F).
[0057] Microporous polymer structure The appropriate microporous polymer structure will depend largely on the application the composite membrane will be used in. The microporous polymer structure preferably has good mechanical properties, is chemically and thermally stable in the environment in which the composite membrane will be used, and is resistant to additives used with the impregnated ion exchange material.
[0058] As used herein, the term "microporous" refers to a structure having pores that are not visible to the naked eye. According to various optional embodiments, the pores can have an average pore size of 0.01 to 100 microns, such as 0.05 to 20 microns or 0.1 to 1 micron.
[0059] As used herein, the term "microporous layer" is intended to refer to a layer having a thickness of at least 0.1 microns, optionally from 0.5 to 100 or 1 to 50 microns, and having an average pore size of from 0.05 to 20 microns, for example, from 0.1 to 1 micron.
[0060] The microporous polymer structure 105 suitable for fuel cell applications can include porous polymer materials. The porous polymer materials can include fluoropolymers, chlorinated polymers, hydrocarbons, polyamides, polycarbonates, polyacrylates, polysulfones, copolyetheresters, polyethylene, polypropylene, polyvinylidene fluoride, polyaryletherketones, polybenzimidazoles, poly(ethylene-co-tetrafluoroethylene), poly(tetrafluoroethylene-co-hexafluoropropylene). In some embodiments, the microporous polymer structure 105 includes perfluorinated porous polymer materials. The perfluorinated porous polymer materials can include polytetrafluoroethylene (PTFE), expanded polytetrafluoroethylene (ePTFE), polyvinylidene fluoride (PVDF), expanded polyvinylidene fluoride (ePVDF), expanded poly(ethylene-co-tetrafluoroethylene) (eEPTFE), or mixtures thereof.
[0061] In some embodiments, the microporous polymer structure 105 comprises a hydrocarbon material, which may include polyethylene, expanded polyethylene, polypropylene, expanded polypropylene, polystyrene, polycarbonate, track-etched polycarbonate, or mixtures thereof. An example of a perfluorinated porous polymer material suitable for use in fuel cell applications includes ePTFE made according to the teachings of U.S. Patent No. 8,757,395, which is incorporated herein by reference in its entirety, and is commercially available in various forms from W. L. Gore & Associates, Inc. of Elkton, Md.
[0062] Ion Exchange Materials Suitable ion exchange materials may depend on the application in which the composite membrane is used. The ion exchange material preferably has a low equivalent weight (e.g., 460 cc / eq or less) and is chemically and thermally stable in the environment in which the composite membrane is used. Ionomers suitable for fuel cell applications may include ion exchange materials such as cation exchange materials, anion exchange materials, or ion exchange materials that include both cation and anion exchange capabilities. In some embodiments, the ion exchange material includes a proton conducting polymer or a cation exchange material. Ion exchange materials include perfluorocarboxylic acid polymers, perfluorophosphonic acid polymers, styrene ion exchange polymers, fluorostyrene ion exchange polymers, polyaryletherketone ion exchange polymers, polysulfone ion exchange polymers, bis(fluoroalkylsulfonyl)imides, (fluoroalkylsulfonyl)(fluorosulfonyl)imides, polyvinyl alcohol, polyethylene oxide, divinylbenzene, metal salts with or without polymers, and mixtures thereof. Examples of perfluorosulfonic acid polymers suitable for use in fuel cell applications include Nafion® (EI DuPont de Nemours, Inc., Wilmington, DE, US), Flemion® (Asahi Glass Co. Ltd., Tokyo, JP), Aciplex® (Asahi Chemical Co. Ltd., Tokyo, JP), Aquivion® (SolvaySolexis SPA, Italy) and 3M™ (3M Innovative Properties Company, USA), which are commercially available perfluorosulfonic acid copolymers. Other examples of perfluorosulfonic acid polymers suitable for use in fuel cell applications include perfluorinated perfluorinated sulfonyl (co)polymers, such as those described in U.S. Pat. No. 5,463,005.
[0063] Composite membrane properties As described below, the composite membranes 100, 200, 300 include a microporous polymer structure 105 and an ion exchange material 110 absorbed in the microporous polymer structure, thereby forming two distinct materials that achieve improved durability and selectivity of the composite membranes 100, 200, 300. The durability is affected by the volume of the microporous polymer structure 105 compared to the total volume of the composite membranes 100, 200, 300. The durability of the composite membranes can be measured as a burst strength that can be greater than 0.2 N, for example, greater than 0.5 N, or greater than 1 N, for example, 0.2 N to 10 N, 1 to 10 N.
[0064] To achieve high selectivity, the conductance may be high and the permeance may be low. In some exemplary embodiments, the conductance of the composite membrane can be measured as ionic conductivity (e.g., proton conductance) per unit thickness. Conductance is optionally measured as 1 Siemens / cm, as determined by the proton conductance test described herein at 50% relative humidity. 2 Larger, e.g. 10 Siemens / cm 2 Greater than or equal to 14 Siemens / cm 2 The permeance of the composite membrane can be measurable as permeability per unit thickness (e.g., hydrogen permeance). The permeance is optionally greater than 400 mA / (Mpa*cm) as determined by the Hydrogen Permeance Test described herein at 50% relative humidity. 2 ) or less, for example, 300mA / (Mpa*cm 2 ) or less than 190mA / (Mpa*cm 2 In some embodiments, the selectivity of the composite membrane is greater than 0.05 MPa / mV, e.g., greater than 0.2 MPa / mV, or greater than 0.35 MPa / mV, or greater than 0.5 MPa / mV, based on the conductance and permeance of the composite membrane at 50% relative humidity. In terms of ranges, the selectivity is optionally between 0.05 and 5 MPa / mV, e.g., between 0.2 and 5 MPa / mV, or between 0.4 and 5 MPa / mV, or between 1 and 5 MPa / mV.
[0065] Durability and selectivity of the composite membrane 100, 200, 300 can be achieved by various aspects of the present disclosure while maintaining the current levels of conductance and ultrathin profile to which customers are accustomed. In particular, increasing the relative volume of the microporous polymer structure 105 to achieve the desired durability may (i) increase the thickness of the composite membrane 100, 200, 300, deviating from the ultrathin profile, and / or (ii) adversely affect the acid content of the composite membrane 100, 200, 300, compromising conductance. Utilizing two distinct materials (i.e., microporous polymer structure and ionomer), in combination with an ionomer having the desired equivalent weight properties, allows the volume of the microporous polymer structure to be increased relative to the total volume of the composite, thus improving durability. Additionally, the ionomer maintains a low equivalent weight of the composite membrane, thereby compensating for the dilution of the ionomer caused by the increased volume of the microporous polymer structure, thereby maintaining the overall membrane acid content and the overall composite membrane thickness.
[0066] In some embodiments, the microporous polymer structure 105 occupies more than 13%, such as more than 18% or more than 30%, of the total volume of the composite membrane at 0% relative humidity. In other embodiments, the microporous polymer structure 105 occupies between 13% and 65%, between 13% and 45%, such as between 18% and 36%, or between 18% and 28%, of the total volume of the composite membrane at 0% relative humidity. In some embodiments, the equivalent volume of the ion exchange material 110 is less than 460 cc / equivalent, such as between 255 cc / molar equivalent and 460 cc / molar equivalent. In various embodiments, the acid content of the composite membrane 100, 200, 300 is greater than 1.2 meq / cc at 0% relative humidity, such as between 1.2 meq / cc and 3.5 meq / cc. In various embodiments, the thickness of the composite membrane 100, 200, 300 is less than 17 microns at 0% relative humidity, such as between 1 micron and 17 microns. Specifically, according to embodiments, the thickness of the composite membrane 100, 200, 300 is less than the threshold thickness of 17 microns, while the acid content of the composite membrane 100, 200, 300 is maintained between 1.2 meq / cc and 3.5 meq / cc.
[0067] The volume percent of the microporous polymer structure in the composite refers to the space occupied by the nodes and fibrils of the microporous polymer structure without the ionomer. Therefore, the volume percent of the microporous polymer structure in the composite is different from the absorbent layer that contains the ionomer. The volume percent of the microporous polymer structure in the composite is affected by humidity. Therefore, the experiments discussed below are performed in dry conditions (e.g., 50% relative humidity (RH)).
[0068] The equivalent weight of ion exchange materials is also affected by humidity, therefore the experiments discussed below, performed in dry conditions under ideal conditions, and in the presence of water, do not affect the equivalent volume values and allow meaningful comparisons to be made between different ionomers.
[0069] The total acid concentration of the composite membrane is calculated based on volume, not mass, to provide a method of meaningful comparison between composite membranes containing ionomers and microporous polymer structures of different densities. As noted above, mass-based measurements have important limitations when correlating with proton conductivity, in part because different polymers have significantly different densities. Furthermore, conduction occurs on length scales and is therefore better represented by volume-based measurements rather than mass-based measurements. The total acid concentration is averaged over the composite membrane. Because the total acid concentration is also affected by humidity, the experiments discussed below are performed under ideal (e.g., clean) dry conditions (e.g., 50% relative humidity (RH)).
[0070] It is understood that the selectivity of the composite membrane can be increased by increasing the overall acid content. However, increasing the overall acid content decreases the mechanical durability of the composite membrane. Therefore, increasing the acid content is not a preferred method for increasing selectivity.
[0071] As described above, it is surprising and unexpected that the selectivity of the composite membrane is dramatically improved by increasing the content of the microporous polymer structure while keeping the apparent equivalent weight constant. The improvement in selectivity is achieved by increasing the microporous structure content in the composite membrane while maintaining the thickness and acid content of the composite material within a predetermined range or within a predetermined range. That is, the embodiment provides a composite membrane having a predetermined thickness (i.e., less than 17 microns thick) while having an acid content of 1.2 meq / cc to 3.5 meq / cc, and consisting of 13% to 65% by volume of the microporous structure.
[0072] The improvement in selectivity is illustrated in Figures 3A-3B, which provide graphs 300 and 350 comparing the selectivity of the comparable composite membranes to the selectivity of the composite membranes of the present invention. Referring to Figure 3A, each line 302-328 relates to the selectivity data of each series of examples, which will be discussed in more detail below. Specifically, each line 302-328 relates the selectivity data points of the comparable examples to the selectivity data points of the corresponding inventive examples. Thus, the lines themselves are provided to guide the eye and do not represent the data themselves. The data for the thirteenth series of examples does not have an inventive example, and therefore the selectivity of the comparative example is represented by a single selectivity data point rather than a line. As shown in graph 300, the selectivity of the composite membrane in each inventive example is dramatically improved compared to the selectivity of the corresponding comparative composite membrane.
[0073] Figure 3B shows the selectivity data normalized to the comparative example. Thus, in the graph 350 shown in Figure 3B, the selectivity of the comparative example for each exemplary series is normalized to zero. The selectivity of the inventive example for each series is shown as a data point and is related to the selectivity of the corresponding comparative example. As shown in graph 350, the selectivity of the composite membrane in each inventive example is dramatically improved compared to the selectivity of the corresponding comparative composite membrane.
[0074] II. Preparation method of composite membrane 4A-4C illustrate example flow diagrams of methods 410, 420, and 430 for manufacturing an example composite membrane (e.g., composite membrane 100 discussed with respect to FIGS. 1A-1G, composite membrane 200 discussed with respect to FIGS. 2A-2C, or composite membrane 300 discussed with respect to FIGS. 2D-2F), according to various aspects of the present disclosure. The flow diagrams illustrate the architecture, functionality, and operation of possible implementations of systems and methods according to various embodiments of the present disclosure. In some alternative implementations that make logical sense, the functions noted in each block may occur in an order different from the order noted in the figures. For example, two blocks shown in succession may in fact be executed substantially simultaneously, or the blocks may sometimes be executed in the reverse order, depending on the functions, methods, or end products involved.
[0075] Referring to FIG. 4A, an exemplary flow diagram of method 410 shows a method for forming a composite material having a fully imbibed microporous polymer structure and two additional layers of ion exchange material. Method 410 includes providing a support structure, such as a backer. Suitable support structures can include woven materials, such as, for example, scrims made from woven fibers of expanded porous polytetrafluoroethylene, webs made from extruded or oriented polypropylene or polypropylene netting, commercially available from Conwed, Inc. of Minneapolis, Minn, woven polypropylene and polyester materials from Tetko Inc. of Briarcliff Manor, NY. Suitable nonwoven materials can include, for example, spunbond polypropylene from Reemay Inc. of Old Hickory, Tenn. In other embodiments, the support structure may include a web of polyethylene ("PE"), polystyrene ("PS"), cyclic olefin copolymer ("COC"), cyclic olefin polymer ("COP"), fluorinated ethylene propylene ("FEP"), perfluoroalkoxyalkane ("PFA"), ethylene tetrafluoroethylene ("ETFE"), polyvinylidene fluoride ("PVDF"), polyetherimide ("PEI"), polysulfone ("PSU"), polyethersulfone ("PES"), polyphenylene oxide ("PPO"), polyphenylether ("PPE"), polymethylpentene ("PMP"), polyethylene terephthalate ("PET"), or polycarbonate ("PC").In some embodiments, the support structure also includes a protective layer that can include polyethylene (PE), polystyrene ("PS"), cyclic olefin copolymer ("COC"), cyclic olefin polymer ("COP"), fluorinated ethylene propylene ("FEP"), perfluoroalkoxyalkane ("PFA"), ethylene tetrafluoroethylene ("ETFE"), polyvinylidene fluoride ("PVDF"), polyetherimide ("PEI"), polysulfone ("PSU"), polyethersulfone ("PES"), polyphenylene oxide ("PPO"), polyphenylether ("PPE"), polymethylpentene ("PMP"), polyethylene terephthalate ("PET"), or polycarbonate ("PC"). In yet other embodiments, the support structure can include a support structure that can optionally include a reflective layer that includes a metal substrate (e.g., an aluminum substrate). The particular metal selected can vary widely, so long as it is reflective. A non-limiting list of exemplary metals includes aluminum, beryllium, cerium, chromium, copper, germanium, gold, hafnium, manganese, molybdenum, nickel, platinum, rhodium, silver, tantalum, titanium, tungsten, zinc, or alloys such as Inconel or bronze. The reflective layer may optionally include a mixture or alloy of two or more metals, and may optionally include two or more of the above metals. The reflective layer may optionally include a highly reflective polymeric multilayer film, such as Vikuiti™ Enhanced Specular Reflector available from 3M Company. In yet another example, the reflective layer may optionally include a highly reflective non-metallic inorganic dielectric multilayer film, including materials such as magnesium fluoride, calcium fluoride, titanium dioxide, silicon dioxide, and the like.
[0076] In step 440, the first ionomer solution is applied to the support structure as a layer of controlled thickness in a single-pass or multi-pass ionomer coating technique, including forward roll coating, reverse roll coating, gravure coating, doctor coating, kiss coating, slot die coating, slide die coating, as well as dipping, brushing, painting, and spraying. The first ionomer solution may be prepared by dissolving an ion exchange material in a solvent. The first ionomer solution includes an ion exchange material and a solvent, and may optionally include additional components, such as a surfactant. In some embodiments, the ion exchange material is a cation exchange material, an anion exchange material, or an ion exchange material that includes both cation and anion exchange capabilities. The choice of solvent may depend, in part, on both the composition of the ionomer and the composition of the porous substrate.
[0077] In step 442, the untreated microporous polymer structure is laminated onto at least a portion of the first ionomer solution by any conventional technique, such as, for example, hot roll lamination, ultrasonic lamination, adhesive lamination, contact lamination, or forced hot air lamination, so long as the technique does not damage the integrity of the untreated microporous polymer structure. In some embodiments, the untreated microporous polymer structure comprises ePTFE having a microporous polymer structure. The microporous polymer structure can be characterized by a uniform structure and composition throughout its thickness. In other aspects, the structure and composition of the microporous polymer structure can vary throughout its thickness. The prepared or obtained microporous polymer structure can have a thickness of less than 200 microns at 0% relative humidity, for example, between 1 micron and 50 microns. The mass per unit area of the untreated microporous polymer structure can be less than 0.05 g / m at 0% relative humidity. 2 Larger, e.g. 0.3g / m 2 ~20g / m 2 It can be.
[0078] For example, a carrier support such as a backer can be continuously fed from a roller unwinding station to a coating station via registration and tension rollers. The ionomer solution can be applied as a layer of controlled thickness onto the surface of the carrier support (backer) by a suitable coating means such as, for example, a doctor blade. The untreated microporous polymer structure is continuously fed from the roller unwinding station to the registration rollers, which contact the coated carrier support and are impregnated with the ionomer solution. Alternatively, the carrier support can be eliminated and a layer of ionomer solution can be applied directly to the untreated microporous polymer structure.
[0079] In step 444, the treated microporous polymer structure is placed in an oven to dry and complete the construction of the composite membrane. The oven temperature can be greater than 60° C., for example, between 60° C. and 200° C. or between 120° C. and 180° C. Drying the treated microporous polymer structure in the oven causes the ion exchange material to adhere firmly to the internal membrane surfaces, such as the fibrils and / or nodes of the microporous polymer structure, and optionally to the external membrane surfaces. The resulting dried composite membrane can have a thickness of less than 17 microns, for example, between 0.1 microns and 17 microns, at 0% relative humidity. The composite membrane can have a mass of 0.2 g / m at 0% relative humidity. 2 Larger, e.g., 0.2 g / m 2 ~40g / m 2 It can be.
[0080] In step 446, a second ionomer solution can be coated onto the dried composite material. Similar to step 440, the second ionomer solution can be applied to the composite material as a layer of controlled thickness by single-pass or multi-pass ionomer coating techniques including forward roll coating, reverse roll coating, gravure coating, doctor coating, kiss coating, slot die coating, slide die coating, as well as dipping, brushing, painting, and spraying. The second ionomer solution can be prepared by dissolving an ion exchange material in a solvent. The second ionomer solution can include an ion exchange material and a solvent, and can optionally include additional components such as surfactants. In some embodiments, the ion exchange material is a cation exchange material, an anion exchange material, or an ion exchange material that includes both cation exchange and anion exchange capabilities. In some embodiments, the second ionomer solution can be the same as the first ionomer solution. Alternatively, the second ionomer solution can be different from the first ionomer solution.
[0081] In step 448 , similar to step 444 , the structure is placed in an oven to dry and finish constructing the composite membrane 100 .
[0082] 4B, an exemplary flow diagram of method 420 illustrates a method of forming a composite material having two fully imbibed microporous polymer structures in contact with one another and two additional layers of ion exchange material. Method 420, like method 410, includes providing a support structure (e.g., a backer), such as a woven material.
[0083] In step 450, the first ionomer solution is applied as a layer of controlled thickness to a supporting structure (backer), similar to step 440 of method 410. The description of step 450 is the same as step 440 of method 410 above, and therefore will not be repeated here.
[0084] In step 452, a first untreated microporous polymer structure (layer 1) is laminated onto a first portion of the first ionomer solution, and a second untreated microporous polymer structure (layer 2) is laminated onto the same portion of the first ionomer solution on layer 1 by any conventional technique, such as hot roll lamination, ultrasonic lamination, adhesive lamination, contact lamination, or forced hot air lamination, so long as it does not damage the integrity of the microporous polymer structure. In some embodiments, the first and second untreated microporous polymer structures include ePTFE having a microporous polymer structure. In some embodiments, the second untreated microporous polymer structure can be the same as the first untreated microporous polymer structure. Alternatively, the second untreated microporous polymer structure can be different from the first untreated microporous polymer structure. The first and second microporous polymer structures can be characterized by a uniform structure and composition throughout their thickness. In other embodiments, the structure and composition of the first and second microporous polymer structures may vary throughout their thickness.
[0085] Steps 454-458 are similar to steps 444-448 of method 410. Therefore, description of steps 454-458 is omitted here. The dried prepared or obtained microporous polymer structure can have a thickness of less than 200 microns at 0% relative humidity, for example, 1 micron to 50 microns. The mass per unit area of the untreated microporous polymer structure can be less than 0.05 g / m at 0% relative humidity. 2 Larger, e.g. 0.3g / m 2 ~20g / m 2 It can be.
[0086] 4C, an exemplary flow diagram of method 430 illustrates a method of forming a composite material having two fully imbibed microporous polymeric structural layers and two additional layers of ion exchange material, separated from each other by another layer of ion exchange material. Method 430, similar to methods 410 and 420, includes providing a support structure (e.g., a backer), such as a woven material.
[0087] Steps 460-466 of method 430 are identical to steps 440-446, respectively, of method 410. Therefore, a description of steps 460-466 will be omitted here.
[0088] In step 468, a second untreated microporous polymer structure is laminated onto at least a portion of the second ionomer solution by any conventional technique, such as, for example, hot roll lamination, ultrasonic lamination, adhesive lamination, contact lamination, or forced hot air lamination, so long as the technique does not damage the integrity of the untreated porous substrate. In some embodiments, the second untreated microporous polymer structure comprises ePTFE having a microporous polymer structure. In some embodiments, the second untreated microporous polymer structure can be the same as the first untreated microporous polymer structure. Alternatively, the second untreated microporous polymer structure can be different from the first untreated microporous polymer structure. The first and second microporous polymer structures can be characterized by a uniform structure and composition throughout their thickness. In other aspects, the structure and composition of the first and second microporous polymer structures can vary throughout their thickness.
[0089] In step 470, the treated microporous polymer structure is placed in an oven to dry, similar to step 444 of method 410. The prepared or resulting microporous polymer structure can have a thickness of less than 200 microns, for example, 1 to 50 microns, at 0% relative humidity. The mass per unit area of an untreated microporous polymer structure can be less than 0.05 g / m at 0% relative humidity. 2 Larger, e.g. 0.3g / m 2 ~20g / m 2 It can be.
[0090] In step 474, a third ionomer solution can be coated onto the dried composite material, similar to step 460. In some embodiments, the third ionomer solution can be the same as the first and / or second ionomer solutions. Alternatively, the third ionomer solution can be different from the first and second ionomer solutions.
[0091] In step 474 , similar to step 448 , the treated microporous polymer structure is placed in an oven to dry and complete the construction of the composite membrane 300 .
[0092] Methods 410, 420 and 430 can be repeated as desired to form a multi-layer composite membrane.
[0093] III. MEA and Fuel Cells As shown in Figures 5A and 5B, a composite membrane constructed as discussed with respect to Figures 1A-2F and described in Figures 4A-4C can be incorporated into an MEA 500 and a fuel cell 580. In some embodiments, a composite membrane constructed as discussed with respect to Figures 1A-2F and described in Figures 4A-4C can be incorporated into a redox flow battery.
[0094] 5A, in some embodiments, the MEA 500 includes a composite membrane 505 (e.g., composite membranes 100, 200, 300) sandwiched between two catalyst-imbibed electrodes 510, 515. The electrodes 510, 515 are electrically insulated from one another by the composite membrane 505 and constitute the anode 510 and cathode 515 of the MEA 500. Optionally, the MEA 500 can further include gas diffusion layers 520, 525, such as carbon paper or carbon cloth.
[0095] As shown in FIG. 5B, in some embodiments, the fuel cell 580 includes an MEA 500 including a composite membrane 505 (e.g., composite membranes 100, 200, 300) sandwiched between a catalyst-imbibed anode 510 and a cathode 515. Optionally, the MEA 500 can further include gas diffusion layers 520, 525, such as carbon paper or carbon cloth. The anode 510 is configured to oxidize a fuel 535 (e.g., hydrogen fuel) into ions 540 and electrons 545. The ions 540 can diffuse through the composite membrane 505 to the cathode 515. When the ions 540 reach the cathode 515, the ions 540 react with an oxidant 550 (e.g., oxygen) to produce water. The electrons 545 can pass through a circuit 555 to produce electricity. Thus, electricity is formed at a load 560, and water is obtained as a by-product.
[0096] IV. Examples A. Test Procedures and Measurement Protocols Used in the Examples Bubble Point Bubble point was measured according to the procedure of ASTM F316-86. Isopropyl alcohol was used as the wetting fluid to fill the pores of the specimen. The bubble point is the pressure of air required to create the first continuous stream of air bubbles detectable rising through a layer of isopropyl alcohol covering a microporous polymer matrix. This measurement provides an estimate of the maximum pore size.
[0097] Girlie Number Gas flow barrier properties were measured using a Gurley Density Meter according to ASTM D-726-58. The procedure involves clamping the sample between the breathable plates of the Gurley Density Meter. An inner cylinder of known weight is then released, which is allowed to slide freely. The Gurley Number is defined as the time in seconds it takes for the released inner cylinder to displace a specific volume of air in the density meter through the sample material.
[0098] Gas permeability (ATEQ) An ATEQ Corp. Premier D Compact Flow Tester was used to measure the air flow rate (liters / hour) through each microporous polymer structure when challenged with a differential pressure of 1.2 kPa (12 mbar). The samples were constructed with a flow path cross-sectional area of 2.9 cm. 2 The plate was clamped between the two plates so that
[0099] Non-contact thickness A sample of the microporous polymer structure was placed on a flat, smooth metal anvil and tensioned to remove wrinkles. The height of the microporous polymer structure on the anvil was measured and recorded using a non-contact Keyence LS-7010M digital micrometer. The height of the anvil without the microporous polymer matrix was then recorded. The thickness of the microporous polymer structure was taken as the difference between the micrometer readings with and without the microporous structure present on the anvil.
[0100] Mass per area Each microporous polymer structure was strained sufficiently to remove wrinkles and then cut using a die to a length of 10 cm. 2 A piece was cut out. 10cm 2 The pieces were weighed on a conventional laboratory scale. The mass per area (M / A) was then calculated as the ratio of measured mass / known area. This procedure was repeated twice and the average M / A was calculated.
[0101] Apparent density of the microporous layer The apparent density of the microporous polymer structure was calculated using the non-contact thickness and mass per area data using the following formula:
number
[0102] Solids concentration of a solution of ion exchange material (IEM) In this specification, the terms "solution" and "dispersion" are used interchangeably when referring to the IEM. This test procedure is appropriate for solutions in which the IEM is in proton form and other solids are in negligible amounts. A volume of 2 cubic centimeters of IEM solution was drawn into a syringe and the mass of the syringe containing the solution was measured via the balance of a solid analyzer (obtained from CEM Corporation, USA). The mass of two sheets of fiberglass paper (obtained from CEM Corporation, USA) was also measured and recorded. The IEM solution was then deposited from the syringe onto two layers of fiberglass paper. The fiberglass paper containing the ionomer solution was placed in a solid analyzer and heated to 160°C to remove the solvent liquid. When the mass of the fiberglass paper and the residual solids no longer changed with increasing temperature and time, it was recorded. It is assumed that the residual IEM contains no water (i.e., the ionomer mass corresponding to 0% RH). The mass of the empty syringe was then measured and recorded using the same balance as above. The ionomer solids in the solution were calculated according to the following formula:
number
[0103] Equivalent Weight (EW) of IEM The following test procedure is appropriate for IEMs containing a single ionomer resin or a mixture of ionomer resins that are in proton form (i.e., contain negligible amounts of other cations) and in solution with negligible protonic acids and other ionic species including dissociated salts. If these conditions are not met, the solution must be purified from ionic impurities prior to testing according to appropriate procedures known to those skilled in the art, or the impurities must be characterized and corrected for their effect on the EW test results.
[0104] As used herein, the EW of an IEM refers to when the IEM is in its proton form at 0% RH with negligible impurities. The IEM can contain a single ionomer or a mixture of ionomers in proton form. An amount of IEM solution with a solids concentration determined as above containing 0.2 grams of solids was poured into a plastic cup. The mass of the ionomer solution was measured via a conventional laboratory scale (obtained from Mettler Toledo, LLC, USA). Next, 5 ml of deionized water and 5 ml of 200 proof denatured ethanol (SDA 3C, Sigma Aldrich, USA) are added to the ionomer solution in the cup. Next, 55 ml of 2N sodium chloride solution in water was added to the IEM solution. The sample was then allowed to equilibrate for 15 minutes with constant stirring. After the equilibration step, the sample was titrated with 1N sodium hydroxide solution. The volume of 1N sodium hydroxide solution required to neutralize the sample solution to a pH value of 7 was recorded. The EW of the IEM was measured using a 1N sodium hydroxide solution. IEM ) was calculated as follows:
number
[0105] When multiple IEMs were combined to produce a composite membrane, the average EW of the IEMs in the composite membrane was calculated using the following formula:
number
[0106] Equivalent Volume (EV) of Ion Exchange Material As used herein, the equivalent volume of an IEM refers to the EV when the IEM is pure, in its proton form at 0% RH, and contains negligible impurities. The EV was calculated according to the following formula:
number
[0107] The equivalent weight of each IEM was determined according to the procedure described above. The IEM used in these applications was a perfluorosulfonic acid ionomer resin, and the bulk density of the perfluorosulfonic acid ionomer resin was taken to be 1.96 g / cc at 0% RH.
[0108] Composite membrane thickness The composite film was equilibrated in the room where the thickness was to be measured for at least 1 hour prior to the measurement. The composite film was left attached to the substrate on which it was coated. For each sample, the composite film on the coated substrate was placed on a smooth, flat, and level marble slab. A thickness gauge (obtained from Heidenhain Corporation, USA) was contacted with the composite film and height readings of the gauge were recorded at six different spots arranged in a grid pattern on the film. The sample was then removed from the substrate and the gauge was contacted with the substrate and height readings were again recorded at the same six spots. The thickness of the composite film at a given relative humidity (RH) in the room was calculated as the difference between the height readings of the gauge with and without the composite film present. A RH probe (obtained from Fluke Corporation) was used to measure the local RH. The thickness at 0% RH was calculated using the following general formula:
number
number
[0109] Microporous polymer matrix (MPM) volume content of composite membranes The volume percent of the microporous polymer matrix in each composite membrane was calculated according to the following formula:
number
[0110] Acid content of composite membranes The acid content of the composite membrane was calculated according to the following formula:
number
[0111] Ball burst testing of composite membranes The mechanical strength of the composite membrane prepared according to the present invention was measured by applying a load pressure to the sample.
[0112] The sample was fixed taut in a frame with an opening of 45 mm in diameter. The sample in the frame was placed in a Shimadzu general-purpose testing machine AG-I, Japan, in an environmentally controlled chamber with temperature and relative humidity of 23°C and 80%, respectively. A steel ball of 1 mm in diameter supported by a support was pressed into the suspended membrane at a constant speed of 100 mm / min. The maximum load generated by the system at the time of sample rupture was recorded. The value is called the ball burst strength.
[0113] Composite membrane membrane electrode assembly (MEA) To measure the proton and hydrogen transport resistance through the composite membrane samples of the present invention, a 1.27 cm 2MEAs were prepared with active areas A of 0.01 mg / cm2. For each MEA, the area of the composite membrane was oversized to provide a sealing surface. Additionally, the anodes and cathodes were identical and prepared on a release layer by a proprietary ink-based process as used in the manufacture of the PRIMEA® MEMBRANE ELECTRODE ASSEMBLY Series 5580 (WL Gore & Associates, Inc.). Each electrode containing a Pt / C catalyst was coated on the release layer and dried to give a platinum area loading of 0.4 mg / cm2. 2 Electrodes were dry laminated to each side of the composite film using heat and pressure (160° C. and 100 psi for 3 minutes) and the release layer was removed.
[0114] Composite membrane H + Resistance and H2 resistance As used herein, “proton resistance” (or H +The term "resistance" (or "hydrogen resistance") refers to the inverse of proton conductance, and the term "hydrogen resistance" (or H2 resistance) refers to the inverse of hydrogen permeance. These properties were measured in a single combined test protocol that included a series of electrochemical measurements. These measurements are well known to those skilled in the art, but the actual details of the combined protocol often vary from laboratory to laboratory, and so these actual details are described here. The MEA was prepared as described above, then mounted and sealed in a fuel cell test fixture of proprietary design, with proprietary carbon-based hydrophobic gas diffusion layers (GDLs) on both the anode and cathode sides. The sample and GDLs were compressed between gold-plated flow fields with a mechanical pressure of 184 psi. The fixture was warmed to 80° C., purged with H2 on the anode side and air on the cathode side, and then conditioned according to the teachings of U.S. Patent Application No. US 11043917. After conditioning, the cathode side was purged with N2 and hydrogen and proton resistances were measured at the following relative humidities (RH): 10%, 20%, 40%, 50%, 60% and 80%. At each RH, the samples were equilibrated for 25 min before measurements were taken. Hydrogen resistance was measured by applying a constant potential hold of 1 min at 50 mV intervals from 0.3 V to 0.6 V and averaging the current values during the last 10 s of the hold. The average value of the current generated from the hydrogen crossover XOavg during the anodic and cathodic sweeps was used. The current generated from the hydrogen crossover XOavg was calculated based on the active area and hydrogen partial pressure p H2 and calculate the hydrogen resistance.
number
[0115] The hydrogen permeance can be calculated as follows:
number
[0116] The electrochemical impedance spectra were measured at frequencies ω between 20 kHz and 1 Hz. The high-frequency proton resistance R H+ is the electrode ionic resistance R EIR, the non-ideal double-layer capacitance Q including the non-ideal parameter φ DL The constant phase element, represented by the electrical impedance contributed by the system, Z SYSTEM and the electrical impedance contributed by the gas diffusion medium, Z GDM The measured total impedance Z fitted to the porous electrode equivalent circuit model taking into account TOTAL was calculated by normalizing to the active area.
number
[0117] The proton conductance can then be calculated as follows:
number
[0118] Selectivity of composite membranes The selectivity of the multi-layer composite membrane was calculated according to the following formula:
number
[0119] The selectivity parameter describes how much of a barrier a membrane has to the two transport processes of hydrogen gas and protons that occur in a fuel cell. For a fuel cell to utilize hydrogen gas with high efficiency, it is desirable for the membrane to exhibit as high a resistance to hydrogen gas transport as possible. At the same time, for the fuel cell to be able to achieve high power output, it is desirable for the fuel cell membrane to have as low a proton resistance as possible. As a result, fuel cell membranes with high selectivity values are desirable, as they better utilize hydrogen fuel while providing a higher power output.
[0120] Porosity measurement The porosity in the composite membrane prepared according to the present disclosure can be measured using a combination of a gas pycnometer and a laboratory mass scale. The gas pycnometer can use helium or other gases, including larger molecules such as nitrogen. To obtain accurate results, the use of gases that are absorbed into the material being tested can be avoided. A sample of the composite membrane can be placed in a chamber of known volume. The chamber with the sample inside can be evacuated from atmospheric gases and possible volatile components, such as water, that may be present in the sample. To ensure that the sample and chamber are free of gas or other volatile components, the sample can be equilibrated for 20 minutes at a pressure of less than 0.001 atm. A known volume of inert gas is then placed in the chamber containing the sample. The pressure developed in the sample chamber can then be recorded. The gas from the sample chamber can then be released into an empty chamber of known volume, and the pressure recorded. Using the two pressure readings and the known chamber volume value, the volume of the sample that is inaccessible to gas molecules can be calculated. EXAMPLES
[0121] b.Example The apparatus and methods of manufacture of the present disclosure may be better understood with reference to the following non-limiting examples.
[0122] Determination of properties such as acid content, volume, selectivity and strength of the composite membranes, as well as the test procedures and measurement protocols, were carried out as described above. The table shown in Figure 6 shows the properties of the microporous polymer structures used in the various test procedures in a series of 12 examples according to some aspects of the invention. Each series includes one or more comparative examples and / or inventive examples, as discussed in more detail below. Individual tables showing the properties of the composite membranes are provided in association with each series.
[0123] Ion exchange materials produced according to embodiments of the present disclosure for all examples. All ion exchange materials used in the following examples are perfluorosulfonic acid (PFSA) based ionomers with the specified equivalent volume (EV) in Figure 6. All ionomers prior to fabrication of the composite membranes were in the form of solutions based on a mixture of water and ethanol as solvents, with a water content of less than 50% in the solvent phase.
[0124] The composite membrane of the present disclosure was manufactured using a commonly known ion exchange material. A preferred example is a solution obtained by dispersing or dissolving a solid PFSA ionomer represented by the following general formula (a:b=1:1 to 9:1, n=0, 1 or 2) in a solvent. [ka] In some embodiments, the solvent is selected from the group consisting of water, alcohols such as methanol, ethanol, propanol, n-butyl alcohol, isobutyl alcohol, sec-butyl alcohol and tert-butyl alcohol, hydrocarbon solvents such as n-hexane, ether solvents such as tetrahydrofuran and dioxane, sulfoxide solvents such as dimethyl sulfoxide and diethyl sulfoxide, formamide solvents such as N,N-dimethylformamide and N,N-diethylformamide, acetamide solvents such as N,N-dimethylacetamide and N,N-diethylacetamide, pyrrolidone solvents such as N-methyl-2-pyrrolidone and N-vinyl-2-pyrrolidone, 1,1,2,2-tetrachloroethane, 1,1,1,2-tetrachloroethane, 1,1,1-trichloroethane, 1,2-dichloroethane, trichloroethylene, tetrachloroethylene, dichloromethane and chloroform. In the present disclosure, the solvent is optionally selected from the group consisting of water, methanol, ethanol and propanol. The water and the above solvents may be used alone or in combination of two or more kinds.
[0125] Series 1 Comparative Example 1.1 Comparative Example 1.1 was carried out according to the following procedure. 2An ePTFE membrane 1, having a thickness of 3.6 μm, an apparent density of 0.17 g / cc, and a bubble point of 75.0 psi, was stretched by hand to remove wrinkles and restrained in this state by a metal frame. A first laydown of EV=347 cc / molar equivalent of PSFA solution (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 39.6% water, 41.3% ethanol, 19.1% solids solution composition was then coated onto the top surface of the polymer sheet substrate. The polymer sheet substrate (obtained from DAICEL VALUE COATING LTD., Japan) contained a protective layer of PET and cyclic olefin copolymer (COC) and was oriented so that the COC side was up. The IEM (PFSA solution) coating was obtained using a Meyer bar with a nominal wet coating thickness of 2.6 mils. While the coating was still wet, the ePTFE membrane 1, previously restrained on a metal frame, was laminated to the coating, at which time the IEM solution was absorbed into the pores. The composite was then dried in a convection oven in air at a temperature of 165°C. Upon drying, the microporous polymer structure (ePTFE membrane) was fully absorbed with the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer sheet substrate. In a second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the polymer sheet substrate) using a drawdown bar at a nominal wet coating thickness of 3 mils. The composite was then dried again at 165°C, at which point it was nearly transparent, indicating complete impregnation of the microporous polymer structure. The multilayer composite membrane was fully occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 9.9 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 2.7 vol. %, and an acid content of 2.8 meq / cc.
[0126] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 1.
[0127] Invention Example 1.2 Inventive Example 1.2 was prepared following the same procedure as above and that used for Comparative Example 1.1, except that different materials were used. 2 ePTFE membrane 2 with a thickness of 9.4 μm, an apparent density of 0.33 g / cc, and a bubble point of 56.8 psi was used as the microporous polymer structure. A solution composition of PSFA solution (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China) as IEM with EV=311 cc / molar equivalent, 21.2% water, 62.4% ethanol, and 16.4% solids was coated in the first laydown using a drawdown bar with a nominal wet coating thickness of 4 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 2 mils. The composite membrane was completely occlusive and had a layer of IEM on both sides of the microporous polymer substrate. The resulting composite membrane had a thickness of 9.8 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 14.0 vol. %, and an acid content of 2.8 meq / cc.
[0128] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 1.
[0129] Table 1 shows the results of various test procedures for the composites of Comparative Example 1.1 and Inventive Example 1.2. [Table 1]
[0130] As shown in Table 1, the composite membranes of Examples 1.1 and 1.2 have similar thicknesses (i.e., 9.9 and 9.8 microns, respectively) and the same total acid content (i.e., 2.8 meq / cc). Thus, the composite membranes of Examples 1.1 and 1.2 have similar conductance characteristics as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that variations in the final mass of the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and ion exchange material (e.g., perfluorosulfonic acid resin) produced very different permeance characteristics in the composite membrane. For example, the composite membrane of Example 1.2 showed improved or increased selectivity compared to that of the composite membrane of Example 1.1 (i.e., 1.2 MPA / mV for Example 1.2 compared to 1.0 MPA / mV for Example 1.1 at 50% RH). Surprisingly, the combined selectivity data for Comparative Example 1.1 and Inventive Example 1.2 demonstrates that selectivity increases as the volume percent occupied by the microporous polymer structure increases while keeping the total acid content of the membrane constant. The increase or improvement in selectivity is illustrated by line 302 shown in graph 300 of Figure 3A and graph 350 of Figure 3B.
[0131] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 1.2 compared to Example 1.1, the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) could be reduced in Example 1.2 compared to Example 1.1, thereby increasing the total volume of the microporous polymer structure from 2.7% in Example 1.1 to 14.0% in Example 1.2, resulting in improved reinforcement of the composite membrane and reduced manufacturing costs of the composite membrane (i.e., reducing the final mass of expensive ion exchange material used to manufacture the composite membrane).
[0132] Series 2 Comparative Example 2.1 Comparative Example 2.1 was prepared by the same procedure as used for Comparative Example 1.1, except that a different material was used: a mass per area of 1.2 g / m 2An ePTFE membrane 3 with a thickness of 5.4 μm, an apparent density of 0.23 g / cc, and a bubble point of 38.0 psi was used as the microporous polymer matrix. A solution of IEM with EV=347 cc / molar equivalent (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 39.6% water, 41.3% ethanol, and 19.1% solids was coated in the first laydown using a Meyer bar with a nominal wet coating thickness of 2 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 1.5 mils. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 7.8 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 6.9 vol. %, and an acid content of 2.7 meq / cc.
[0133] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 2.
[0134] Invention Example 2.2 Inventive Example 2.2 was prepared by the same procedure used for Comparative Example 1.1, except that a different material was used: a mass per area of 2.8 g / m 2An ePTFE membrane 4 with a thickness of 9.6 μm, an apparent density of 0.29 g / cc, and a bubble point of 34.4 psi was used as the microporous polymer matrix. A solution of IEM with EV=311 cc / molar equivalent (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), with a solution composition of 21.2% water, 62.4% ethanol, and 16.4% solids, was coated in the first laydown using a drawdown bar with a nominal wet coating thickness of 3 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 1 mil. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 8.0 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 15.5 vol. %, and an acid content of 2.7 meq / cc.
[0135] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 2. Surprisingly, the combined selectivity data for Comparative Examples 1.1, 2.1 and Inventive Examples 1.2, 2.2 demonstrated that, regardless of the microporous polymer structure used, the selectivity increased as the volume percent occupied by the microporous polymer structure increased while holding the total acid content of the membrane constant.
[0136] Table 2 shows the results of various test procedures for the composites of Comparative Example 2.1 and Inventive Example 2.2. [Table 2]
[0137] As shown in Table 2, the composite membranes of Examples 2.1 and 2.2 have similar thicknesses (i.e., 7.8 and 8 microns, respectively) and the same total acid content (i.e., 2.7 meq / cc). Thus, the composite membranes of Examples 2.1 and 2.2 have similar conductance characteristics as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that variations in the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) produce very different permeance characteristics in the composite membrane. For example, the composite membrane of Example 2.2 showed an improvement or increase in selectivity compared to that of the composite membrane of Example 2.1 (i.e., 1.9 MPA / mV for Example 2.2 compared to 0.8 MPA / mV for Example 2.1 at 50% RH). The increase or improvement in selectivity is shown by line 304 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0138] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 2.2 compared to Example 2.1, it was possible to lower the final mass of the composite membrane (e.g., perfluorosulfonic acid resin) in Example 2.2 compared to Example 2.1, thereby increasing the total volume of the microporous polymer structure from 6.9% in Example 2.1 to 15.5% in Example 2.2, resulting in improved reinforcement of the composite membrane and lowering the manufacturing cost of the composite membrane (i.e., reducing the final mass of expensive ion exchange material used to manufacture the composite membrane).
[0139] Series 3 Comparative Example 3.1 Comparative Example 3.1 was prepared by the same procedure used for Comparative Example 1.1, except that a different material was used: a mass per area of 0.6 g / m 2ePTFE membrane 1, with a thickness of 3.6 μm, an apparent density of 0.17 g / cc, and a bubble point of 75.0 psi, was used as the microporous polymer matrix. A solution of IEM with EV=458 cc / molar equivalent (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 15.3% water, 61.7% ethanol, and 23% solids was coated in the first laydown using a Mayer bar with a nominal wet coating thickness of 3 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 4 mils. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multilayer composite membrane had a thickness of 14.4 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 1.8 vol.%, and an acid content of 2.1 meq / cc.
[0140] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 3.
[0141] Invention Example 3.2 Inventive Example 3.2 was prepared by the same procedure used for Comparative Example 1.1, except that different materials were used: a mass per area of 8.9 g / m 2An ePTFE membrane 4 with a thickness of 25.1 μm, an apparent density of 0.36 g / cc, and a bubble point of 42.7 psi was used as the microporous polymer matrix. A solution of IEM with EV=329 cc / molar equivalent (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 22.0% water, 63.8% ethanol, and 14.2% solids was coated in the first laydown using a Mayer bar with a nominal wet coating thickness of 5.8 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 1 mil. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 14.5 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 27.3 vol. %, and an acid content of 2.2 meq / cc.
[0142] Table 3 shows the results of various test procedures for the composites of Comparative Example 3.1 and Inventive Example 3.2. [Table 3]
[0143] As shown in Table 3, the composite membranes of Examples 3.1 and 3.2 have similar thicknesses (i.e., 14.4 and 14.5 microns, respectively) and similar total acid contents (i.e., 2.1 and 2.2 meq / cc, respectively). Thus, the composite membranes of Examples 3.1 and 3.2 have similar conductance characteristics as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that variations in the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) produce very different permeance characteristics in the composite membrane. For example, the composite membrane of Example 3.2 showed improved or increased selectivity compared to that of the composite membrane of Example 3.1 (i.e., 0.9 MPA / mV for Example 3.2 compared to 0.6 MPA / mV for Example 3.1 at 50% RH). The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 3. Surprisingly, the combined selectivity data of Comparative Example 3.1 and Inventive Example 3.2 show that selectivity increases as the volume percent occupied by the microporous polymer structure increases, even when the membrane is thick and the volume fraction of the microporous polymer structure reaches high levels, approaching 30%. The increase or improvement in selectivity is illustrated by line 306 shown in graph 300 of Figure 3A and graph 350 of Figure 3B.
[0144] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 3.2 compared to Example 3.1, it was possible to reduce the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Example 3.2 compared to Example 3.1, thereby increasing the total volume of the microporous polymer structure from 1.8% in Example 3.1 to 27.3% in Example 3.2, resulting in improved reinforcement of the composite membrane (i.e., ball burst strength of 3.2N in Example 3.2 compared to 1.8N in Example 3.1) and reduced manufacturing costs of the composite membrane (i.e., reduced final mass of expensive ion exchange material used to manufacture the composite membrane).
[0145] Series 4 Comparative Example 4.1 Comparative Example 4.1 was prepared by the same procedure as used for Comparative Example 1.1, except that a different material was used: a mass per area of 0.6 g / m 2 ePTFE membrane 1, with a thickness of 3.6 μm, an apparent density of 0.17 g / cc, and a bubble point of 75.0 psi, was used as the microporous polymer structure. A solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 30.0% water, 60.8% ethanol, and 9.2% solids, with an EV=458 cc / molar equivalent, was coated in the first laydown using a drawdown bar with a nominal wet coating thickness of 4 mils. In the second laydown, a solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 13% water, 74.7% ethanol, and 12.3% solids, with an EV=458 cc / molar equivalent, was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 2 mils. The multi-layer composite membrane was completely occlusive, with a layer of IEM on each side of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 5.5 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 4.9 vol.%, and an acid content of 2.1 meq / cc.
[0146] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 4.
[0147] Invention Example 4.2 Inventive Example 4.2 was prepared by the same procedure used for Comparative Example 1.1, except that different materials were used: a mass per area of 1.9 g / m 2An ePTFE membrane 6 with a thickness of 7.2 μm, an apparent density of 0.27 g / cc, and a bubble point of 137.6 psi was used as the microporous polymer structure. A solution of IEM with EV=413 cc / molar equivalent (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 17.3% water, 71.5% ethanol, and 11.2% solids was coated in the first laydown using a drawdown bar with a nominal wet coating thickness of 4 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 2 mils. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 6.4 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 13.2 vol. %, and an acid content of 2.1 meq / cc.
[0148] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 4.
[0149] Invention Example 4.3 Inventive Example 4.3 was prepared by the same procedure used for Comparative Example 1.1, except that different materials were used: a mass per area of 4.8 g / m 2ePTFE membrane 7 with a thickness of 14.8 μm, an apparent density of 0.33 g / cc, and a bubble point of 68.4 psi was used as the microporous polymer structure. A solution of IEM with EV=311 cc / molar equivalent (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 21.2% water, 62.9% ethanol, and 16.4% solids was coated in the first laydown using a drawdown bar with a nominal wet coating thickness of 3 mils. In the second laydown, a solution of IEM with EV=311 cc / molar equivalent (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 5.1% water, 94.4% ethanol, and 0.5% solids was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 0.5 mils. The multi-layer composite membrane was completely occlusive, with a layer of IEM on each side of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 6.4 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 33.3 vol.%, and an acid content of 2.1 meq / cc.
[0150] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 4. The selectivity data for Comparative Example 4.1 and Inventive Examples 4.2 and 4.3 show that the selectivity increases with increasing volume percentage occupied by the microporous polymer structure, even when the membrane is thick and the volume fraction of the microporous polymer structure is greater than 30%.
[0151] Table 4 shows the results of various test procedures for the composite materials of Comparative Example 4.1 and Inventive Examples 4.2 and 4.3. [Table 4]
[0152] As shown in Table 4, the composite membranes of Examples 4.1, 4.2 and 4.3 have comparable thicknesses (i.e., 5.5, 6.4 and 6.4 microns, respectively) and the same total acid content (i.e., 2.1 meq / cc). Thus, the composite membranes of Examples 4.1, 4.2 and 4.3 have similar conductance characteristics, as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that variations in the final mass of the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and ion exchange material (e.g., perfluorosulfonic acid resin) produce very different permeance characteristics in the composite membrane. For example, the composite membranes of Examples 4.2 and 4.3 showed improved or increased selectivity compared to the selectivity of the composite membrane of Example 4.1 (i.e., 0.6 MPA / mV of Example 4.2 and 0.9 MPA / mV of Example 4.3 compared to 0.5 MPA / mV of Example 4.1 at 50% relative humidity). Combining the data from series 1-4, we show that the addition of an inert microporous polymer structure (in this case ePTFE) improves the fuel cell performance of multi-layer composite membranes used in fuel cell applications while keeping the total acid content of the membrane constant, regardless of the thickness of the multi-layer composite membrane used, or the type of microporous polymer structure used, or what IEM is used. This is a surprising and unexpected discovery. The increase or improvement in selectivity is shown by line 308 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0153] Furthermore, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Examples 4.2 and 4.3 compared to Example 4.1, it was possible to reduce the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Examples 4.2 and 4.3 compared to Example 4.1, which increased the total volume of the microporous polymer structure from 4.9% in Example 4.1 to 13.2% in Example 4.2 and 33.3% in Example 4.3, thereby improving the reinforcement of the composite membrane and reducing the manufacturing cost of the composite membrane (i.e., reducing the final mass of the expensive ion exchange material used to manufacture the composite membrane).
[0154] Series 5 Comparative Example 5.1 Comparative Example 5.1 was prepared by the same procedure as used for Comparative Example 1.1, except that a different material was used: a mass per area of 0.6 g / m 2 ePTFE membrane 1, 3.6 μm thick, 0.17 g / cc apparent density, 75.0 psi bubble point, was used as the microporous polymer matrix. A solution of IEM (D2020 (obtained from Ion Power Inc., USA), 22.1% water, 62.9% ethanol, 15.0% solids) with EV=509 cc / molar equivalent was coated in the first laydown using a Mayer bar with a nominal wet coating thickness of 2.6 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite membrane (opposite surface to the substrate) using a drawdown bar with a nominal wet coating thickness of 3 mils. The resulting multilayer composite membrane had a thickness of 7.9 microns at 0% RH, a volume fraction occupied by the porous polymer structure of 3.4 vol.%, and an acid content of 1.9 meq / cc.
[0155] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 5.
[0156] Invention Example 5.2 Inventive Example 5.2 was prepared by the same procedure used for Comparative Example 1.1, except that a different material was used: a mass per area of 2.2 g / m 2ePTFE membrane 8 was used as the microporous polymer matrix. A solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China) with EV=458 cc / molar equivalent, 20.2% water, 60.0% ethanol, 19.8% solids was coated in the first laydown using a Mayer bar with a nominal wet coating thickness of 2 mils. The same IEM solution in the second laydown was coated on the top surface of the composite membrane (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 1.5 mils. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multilayer composite membrane had a thickness of 7.8 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 12.5 vol.%, and an acid content of 1.9 meq / cc.
[0157] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 5.
[0158] Table 5 shows the results of various test procedures for the composites of Comparative Example 5.1 and Inventive Example 5.2. [Table 5]
[0159] As shown in Table 5, the composite membranes of Examples 5.1 and 5.2 have similar thicknesses (i.e., 7.9 and 7.8 microns, respectively) and the same total acid content (i.e., 1.9 meq / cc). Thus, the composite membranes of Examples 5.1 and 5.2 have similar conductance characteristics, as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that variations in the final mass of the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and ion exchange material (e.g., perfluorosulfonic acid resin) produce very different composite membrane permeance characteristics. For example, the composite membrane of Example 5.2 showed improved or increased selectivity compared to the composite membrane of Example 5.1 (i.e., 0.5 MPA / mV of Example 5.2 compared to 0.4 MPA / mV of Example 5.1 at 50% RH). The increased or improved selectivity is shown by line 310 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0160] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 5.2 compared to Example 5.1, it was possible to lower the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Example 5.2 compared to Example 5.1, thereby increasing the total volume of the microporous polymer structure from 3.4% in Example 5.1 to 12.5% in Example 5.2, resulting in improved reinforcement of the composite membrane and lowering the cost of manufacturing the composite membrane (i.e., reducing the final mass of expensive ion exchange material used to manufacture the composite membrane).
[0161] Series 6 Comparative Example 6.1 Comparative Example 6.1 was prepared by the same procedure as used for Comparative Example 1.1, except that a different material was used: a mass per area of 1.9 g / m 2An ePTFE membrane 6 with a thickness of 7.2 μm, an apparent density of 0.27 g / cc, and a bubble point of 137.6 psi was used as the microporous polymer matrix. A solution of IEM with EV=458 cc / molar equivalent (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 30.0% water, 60.8% ethanol, and 9.2% solids was coated in the first laydown using a drawdown bar with a nominal wet coating thickness of 5 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 2 mils. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 6.4 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 13.1 vol. %, and an acid content of 1.9 meq / cc.
[0162] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 6.
[0163] Invention Example 6.2 Inventive Example 6.2 was prepared by the same procedure used in Comparative Example 1.1, except that a different material was used: a mass per area of 5.8 g / m 2An ePTFE membrane 9 with a thickness of 12.5 μm, an apparent density of 0.46 g / cc, and a bubble point of 32.2 psi was used as the microporous polymer matrix. A solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China) with EV = 311 cc / molar equivalent, 21.2% water, 62.4% ethanol, and 16.4% solids was coated in the first laydown using a Mayer bar with a nominal wet coating thickness of 2 mils. In the second laydown, a solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China) with EV = 311 cc / molar equivalent, 5.1% water, 94.4% ethanol, and 0.5% solids was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 1 mil. The multi-layer composite membrane was completely occlusive, with a layer of IEM on each side of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 6.2 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 41.8 vol.%, and an acid content of 1.9 meq / cc.
[0164] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 6.
[0165] Table 6 shows the results of various test procedures for the composite materials of Examples 6.1 and 6.2 of the present invention. [Table 6]
[0166] As shown in Table 6, the composite membranes of Examples 6.1 and 6.2 have similar thicknesses (i.e., 6.4 and 6.2 microns, respectively) and the same total acid content (i.e., 1.9 meq / cc). Thus, the composite membranes of Examples 6.1 and 6.2 have similar conductance properties as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that the permeance properties of the composite membranes are very different due to variations in the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin). For example, the composite membrane of Example 6.2 showed improved or increased selectivity compared to the composite membrane of Example 6.1 (i.e., 0.7 MPA / mV of Example 6.2 compared to 0.5 MPA / mV of Example 6.1 at 50% RH). The selectivity data for Comparative Example 6.1, Comparative Example 5.1, and Inventive Examples 6.2 and 5.2 show that selectivity increases with thinner membranes and with increasing volume percentage occupied by the microporous polymer structure, even when the microporous polymer structure integration rate exceeds 40%. The increase or improvement in selectivity is shown by line 312 shown in graph 300 of Figure 3A and graph 350 of Figure 3B.
[0167] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 6.2 compared to Example 6.1, it was possible to reduce the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Example 6.2 compared to Example 6.1, which increased the total volume of the microporous polymer structure from 13.1% in Example 6.1 to 41.8% in Example 6.2, resulting in improved reinforcement of the composite membrane and reduced manufacturing costs of the composite membrane (i.e., reduced final mass of expensive ion exchange material used to manufacture the composite membrane).
[0168] Series 7 Comparative Example 7.1 Comparative Example 7.1 was prepared by the same procedure used for Comparative Example 1.1, except that a different material was used: a mass per area of 3.0 g / m 2An ePTFE membrane 10 with a thickness of 15.2 μm, an apparent density of 0.20 g / cc, and a bubble point of 36.6 psi was used as the microporous polymer matrix. A solution of IEM (D2021 obtained from Ion Power Inc., USA) with EV=560 cc / molar equivalent, 26.2% water, 57.3% ethanol, 16.5% solids composition was coated in the first laydown using a drawdown bar with a nominal wet coating thickness of 3 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 1 mil. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multilayer composite membrane had a thickness of 7.1 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 18.8 vol.%, and an acid content of 1.4 meq / cc.
[0169] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 7.
[0170] Invention Example 7.2 Inventive Example 7.2 was prepared by the same procedure used for Comparative Example 1.1, except that different materials were used: a mass per area of 5.8 g / m 2An ePTFE membrane 9 with a thickness of 12.5 μm, an apparent density of 0.46 g / cc, and a bubble point of 32.2 psi was used as the microporous polymer matrix. A solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 13% water, 74.7% ethanol, and 12.3% solids was coated in the first laydown using a drawdown bar with a nominal wet coating thickness of 5 mils. In the second laydown, a solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 5.5% water, 94.0% ethanol, and 0.5% solids was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 1 mils. The multi-layer composite membrane was completely occlusive, with a layer of IEM on each side of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 7.1 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 36.3 vol.%, and an acid content of 1.4 meq / cc.
[0171] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 7.
[0172] Invention Example 7.3 Inventive Example 7.3 was prepared according to the following procedure: First, a 3.1 g / m2 weight per square meter was 2 , ePTFE membrane 2 having a thickness of 9.4 μm, an apparent density of 0.33 g / cc, and a bubble point of 56.8 psi, and a mass per area of 3.0 g / m 2Two microporous polymer structures, ePTFE membranes 10, with a thickness of 15.2, apparent density of 0.20 g / cc, and bubble point of 36.6 psi, were stretched to remove wrinkles and restrained in contact with each other in a metal frame. A first laydown of a solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), EV=413 cc / molar equivalent, 17.3% water, 71.5% ethanol, 11.2% solids composition was then coated onto the top surface of the polymer sheet substrate. The substrate (obtained from DAICEL VALUE COATING LTD., Japan) contained a protective layer of PET and cyclic olefin copolymer (COC) and was oriented so that the COC side was up. The coating was obtained using a Mayer bar with a nominal wet coating thickness of 5 mils. While the coating was still wet, ePTFE membranes 2 and 10, previously restrained to a metal frame, were laminated to the coating, at which time the IEM solution was absorbed into the pores. The multilayer composite was then dried in a convection oven with internal air at a temperature of 165°C. Upon drying, the microporous polymer matrix was fully absorbed with the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer matrix and the substrate. In a second laydown, a solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), EV=413 cc / mol equivalent, 4% water, 95.0% ethanol, 1% solids solution composition was coated onto the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 0.5 mils. The composite was then dried again at 165°C, at which point it was nearly transparent, indicating complete impregnation of the microporous polymer matrix. The multilayer composite included a multilayer composite membrane bonded to a substrate. The multi-layer composite membrane was completely occlusive, with a layer of IEM on each side in contact with the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 6.9 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 39.4 vol.%, and an acid content of 1.5 meq / cc.
[0173] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 7. Table 7 shows the results of various test procedures for the composite materials of Comparative Example 7.1 and Inventive Examples 7.2 and 7.3. [Table 7]
[0174] As shown in Table 7, the composite membranes of Example 7.1 and Examples 7.2 and 7.3 had comparable thicknesses (i.e., 7.1, 7.1 and 6.9 microns, respectively) and similar total acid contents (i.e., 1.4, 1.4 and 1.5 meq / cc, respectively). Thus, the composite membranes of Example 7.1 and Examples 7.2 and 7.3 have similar conductance properties as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that variations in the final mass of the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and ion exchange material (e.g., perfluorosulfonic acid resin) produced very different composite membrane permeance properties. For example, the composite membranes of Examples 7.2 and 7.3 showed improved or increased selectivity compared to that of the composite membrane of Example 7.1 (i.e., 0.4 MPA / mV in Example 7.2 and 0.5 MPA / mV in Example 7.3 at 50% RH compared to 0.3 MPA / mV in Example 7.1). The selectivity data of Comparative Example 7.1 and Inventive Examples 7.2 and 7.3 show that selectivity increases with increasing volume percent occupied by the microporous polymer structure, even when multiple microporous polymer matrices are present in the composite membrane. This is a surprising and unexpected finding. The increase or improvement in selectivity is shown by line 314 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0175] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Examples 7.2 and 7.3 compared to Example 7.1, it was possible to reduce the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Examples 7.2 and 7.3 compared to Example 7.1, which increased the total volume of the microporous polymer structure from 18.8% in Example 7.1 to 36.30% in Example 7.2 and 39.40% in Example 7.3, resulting in improved reinforcement of the composite membrane and reduced manufacturing costs of the composite membrane (i.e., reduced final mass of expensive ion exchange material used to manufacture the composite membrane).
[0176] Series 8 Comparative Example 8.1 Comparative Example 8.1 was prepared by the same procedure used for Comparative Example 1.1, except that a different material was used: a mass per area of 3.0 g / m 2 An ePTFE membrane 10 with a thickness of 15.2 μm, an apparent density of 0.20 g / cc, and a bubble point of 36.6 psi was used as the microporous polymer matrix. A solution of IEM (D2021 obtained from Ion Power Inc., USA) with EV=560 cc / molar equivalent, 25.0% water, 62.5% ethanol, 12.5% solids composition was coated in the first laydown using a Mayer bar with a nominal wet coating thickness of 2 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 0.5 mils. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multilayer composite membrane had a thickness of 4.9 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 27.1 vol.%, and an acid content of 1.3 meq / cc.
[0177] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 8.
[0178] Invention Example 8.2 Inventive Example 8.2 was prepared by the same procedure used for Comparative Example 1.1, except that different materials were used: a mass per area of 4.7 g / m 2 ePTFE membrane 7 with a thickness of 14.0 μm, an apparent density of 0.34 g / cc, and a bubble point of 47.1 psi was used as the microporous polymer matrix. A solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 13% water, 74.7% ethanol, and 12.3% solids was coated in the first laydown using a drawdown bar with a nominal wet coating thickness of 3 mils. In the second laydown, a solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 5.5% water, 94.0% ethanol, and 0.5% solids was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 1 mil. The multi-layer composite membrane was completely occlusive, with a layer of IEM on each side of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 4.9 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 42.6 vol.%, and an acid content of 1.2 meq / cc.
[0179] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 8.
[0180] Table 8 shows the results of various test procedures for the composites of Comparative Example 8.1 and Inventive Example 8.2. [Table 8]
[0181] As shown in Table 8, the composite membranes of Examples 8.1 and 8.2 have the same thickness (i.e., 4.9 microns) and similar total acid content (i.e., 1.3 and 1.2 meq / cc, respectively). Thus, the composite membranes of Examples 8.1 and 8.2 have similar conductance characteristics as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that variations in the final mass of the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and ion exchange material (e.g., perfluorosulfonic acid resin) produce very different composite membrane permeance characteristics. For example, the composite membrane of Example 8.2 showed improved or increased selectivity compared to the composite membrane of Example 8.1 (i.e., 0.4 MPA / mV of Example 8.2 compared to 0.3 MPA / mV of Example 8.1 at 50% RH). Combining the data from Example series 1-8 shows that the addition of an inert microporous polymer structure (in this case ePTFE) and keeping the total acid content of the membrane constant improves fuel cell performance for multilayer composite membranes in the thickness range of 4.9-14.5 microns or for multilayer composite membranes used in fuel cell applications regardless of the type of microporous polymer used, or whether one or more microporous polymers are present or what IEM is used. This is a surprising and unexpected discovery. The increase or improvement in selectivity is shown by line 316 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0182] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 8.2 compared to Example 8.1, it was possible to lower the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Example 8.2 compared to Example 8.1. This increased the total volume of the microporous polymer structure from 27.1% in Example 8.1 to 42.6% in Example 8.2, resulting in improved reinforcement of the composite membrane and lower manufacturing costs of the composite membrane (i.e., reduced final mass of expensive ion exchange material used to manufacture the composite membrane).
[0183] Series 9 Comparative Example 9.1 Comparative Example 9.1 was prepared by the following procedure: A mass per area of 0.6 g / m2An ePTFE membrane 1, 3.6 μm thick, 0.17 g / cc apparent density, and 75.0 psi bubble point, was stretched by hand to remove wrinkles and restrained in this state in a metal frame. A first laydown of a PSFA solution with EV=509 cc / molar equivalent (D2020 obtained from Ion Power Inc., USA), 23.5% water, 60.5% ethanol, 16% solids solution composition was then coated onto the top surface of the polymer sheet substrate. The polymer sheet substrate (obtained from DAICEL VALUE COATING LTD., Japan) contained a protective layer of PET and cyclic olefin copolymer (COC) and was oriented such that the COC side was up. The IEM (PFSA solution) coating was obtained using a Meyer bar with a nominal wet coating thickness of 2.2 mils. While the coating was still wet, the ePTFE membrane 1, previously restrained in a metal frame, was laminated to the coating, during which the IEM solution was absorbed into the pores. The composite was subsequently dried in a convection oven with internal air at a temperature of 165°C. Upon drying, the microporous polymer structure (ePTFE membrane) was fully absorbed into the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer sheet substrate. In a second laydown, a solution of the IEM blend was coated onto the top surface of the composite (opposite surface of the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 2 mils. The solution of the IEM blend was produced by mixing two ionomers, D2020 and D2021 (obtained from Ion Power Inc., USA), in a plastic bottle using a stir bar. First, 9.98 g of D2020 solution containing 21.06 wt% ionomer with EV=509 cc / molar equivalent was poured into the bottle. Next, 10.96 g of a 21.15 wt. % ionomer solution in D2021 with EV=560 cc / molar equivalent was poured into the same bottle. Finally, 914 g of 200 proof ethanol was added to adjust the concentration of solids and solvent in the blend. A magnetic stir bar was placed inside and the bottle was left on a magnetic stir plate for 24 hours. The resulting solution of ion exchange material blend had 14.7 wt. % ionomer solids, 21.6 wt. % water, and 63.7 wt. % ethyl alcohol.The resulting ion exchange material blend had an EV=535 cc / mole equivalent. The composite was then dried again at 165° C., at which point it was nearly transparent, indicating complete impregnation of the microporous polymer structure. The multilayer composite membrane was completely occlusive, with a layer of IEM on each side of the microporous polymer matrix, the layers of IEM having unequal equivalent volumes, and the top layer made from a blend of ionomers. The resulting multilayer composite membrane had a thickness of 7.3 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 3.6 wt %, and an acid content of 1.8 meq / cc.
[0184] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 9.
[0185] Invention Example 9.2 Inventive Example 9.2 was prepared by the same procedure as above and the procedure used for Comparative Example 9.1, but with a mass per area of 3.0 g / m 2A different material with a thickness of 15.2 μm, an apparent density of 0.20 g / cc, and a bubble point of 36.6 psi was used as the microporous polymer matrix. A solution of PSFA as IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China) with EV=413 cc / molar equivalent, 17.3% water, 71.5% ethanol, and 11.2% solids was used to coat in the first laydown using a Meyer bar with a nominal wet coating thickness of 4 mils. In the second laydown, the solution of the IEM blend was coated on the top surface of the composite (the surface opposite the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 3 mils. A solution of the IEM blend was made by mixing PSFA IEM solutions containing two ionomers, EV=413 and EV=458 cc / mol equiv (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China) in a plastic bottle using a stir bar. First, 10.0 g of EV=413 cc / mol equiv of IEM solution containing 21.06 wt% ionomer was poured into the bottle. Next, 5.2 g of EV=458 cc / mol equiv of IEM solution containing 21.15 wt% ionomer was poured into the same bottle. Finally, 30.5 g of 200 proof ethanol and 2.0 g of DI water were added to adjust the concentration of solids and solvents in the blend. A magnetic stir bar was placed inside and the bottle was left on a magnetic stir plate for 24 hours. The resulting ion exchange material blend solution contained 4.5 wt% ionomer solids, 10.0 wt% water, and 85.5 wt% ethyl alcohol. The resulting ion exchange material blend had an EV=434 cc / mol equivalent. The composite membrane was completely occlusive, with a layer of IEM on each side of a microporous polymer substrate, the layers of IEM having unequal equivalent volumes, and the top layer made from the ionomer blend. The resulting composite membrane had a thickness of 7.6 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 17.6 vol%, and an acid content of 2.0 meq / cc.
[0186] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 9.
[0187] Table 9 shows the results of various test procedures for the composites of Comparative Example 9.1 and Inventive Example 9.2. [Table 9]
[0188] As shown in Table 9, the composite membranes of Examples 9.1 and 9.2 have similar thicknesses (i.e., 7.3 and 7.6 microns, respectively) and similar total acid contents (i.e., 1.8 and 2 meq / cc, respectively). Thus, the composite membranes of Examples 9.1 and 9.2 have similar conductance characteristics, as demonstrated by resistivity measurements. However, it has been surprisingly and unexpectedly discovered that variations in the final mass of the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and ion exchange material (e.g., perfluorosulfonic acid resin) produce very different composite membrane permeance characteristics. For example, the composite membrane of Example 9.2 shows improved or enhanced selectivity compared to that of the composite membrane of Example 9.1 (0.6 MPA / mV for Example 9.2 compared to 0.4 MPA / mV for Example 9.1 at 50% RH). The increased or improved selectivity is shown by line 318 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0189] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 9.2 compared to Example 9.1, it was possible to lower the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Example 9.2 compared to Example 9.1, thereby increasing the total volume of the microporous polymer structure from 3.6% in Example 9.1 to 17.6% in Example 9.2, resulting in improved reinforcement of the composite membrane (and reduced manufacturing costs of the composite membrane (i.e., reduced final mass of expensive ion exchange material used to manufacture the composite membrane)).
[0190] Series 10 Comparative Example 10.1 Comparative Example 10.1 was prepared by the following procedure. The mass per area was 0.6 g / m2 An ePTFE membrane 1, 3.6 μm thick, 0.17 g / cc apparent density, and 75.0 psi bubble point, was stretched by hand to remove wrinkles and restrained in this state in a metal frame. A first laydown of EV=560 cc / molar equivalent of PFSA solution as IEM (D2021 obtained from Don Power Inc., USA), 26.2% water, 57.3% ethanol, 16.5% solids solution composition was then coated on the top surface of the polymer sheet substrate. The polymer sheet substrate (obtained from DAICEL VALUE COATING LTD., Japan) contained a protective layer of PET and cyclic olefin copolymer (COC) and was oriented with the COC side facing up. The IEM (PFSA solution) coating was obtained using a Meyer bar with a nominal wet coating thickness of 3.0 mils. While the coating was still wet, the ePTFE membrane 1 previously restrained in a metal frame was laminated to the coating, during which the IEM solution was absorbed into the pores. The composite was subsequently dried in a convection oven at a temperature of 165°C with internal air. Upon drying, the microporous polymer structure (ePTFE membrane) was completely absorbed into the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer sheet substrate. In a second laydown, a solution composition of PFSA solution as IEM (D2020 obtained from Ion Power Inc., USA), 23.5% water, 60.5% ethanol, 16.0% solids, with EV=509 cc / mol equivalent, was coated onto the top surface of the composite (the surface opposite the polymer sheet substrate) using a drawdown bar with a 3 mil nominal wet coating thickness. The composite was then dried again at 165°C, at which point it was nearly transparent, indicating complete impregnation of the microporous polymer structure. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix, and these layers of IEM had unequal equivalent volumes. The resulting multi-layer composite membrane had a thickness of 8.8 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 3.0 vol. %, and an acid content of 1.8 meq / cc.
[0191] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 10.
[0192] Invention Example 10.2 Inventive Example 10.2 was prepared by the same procedure used above and in Comparative Example 10.1, except that a different material was used: a mass per area of 4.8 g / m 2 An ePTFE membrane 11 with a thickness of 14.8 μm, an apparent density of 0.33 g / cc, and a bubble point of 68.4 psi was used as the microporous polymer structure. A solution composition of EV=458 cc / molar equivalent of PSFA solution as IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 20.2% water, 60.0% ethanol, 19.8% solids was used to coat in the first laydown using a drawdown bar with a nominal wet coating thickness of 4 mils. In the second laydown, a solution composition of EV=347 cc / molar equivalent of PFSA solution as IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 39.6% water, 41.3% ethanol, 19.1% solids was used to coat on the top surface of the composite (the surface opposite to the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 1 mils. The composite membrane was completely occlusive, with a layer of IEM on each side of the microporous polymer substrate, the layers of IEM having unequal equivalent volumes. The resulting composite membrane had a thickness of 10.3 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 20.8 vol.%, and an acid content of 1.9 meq / cc.
[0193] Table 10 shows the results of various test procedures for the composites of Comparative Example 10.1 and Inventive Example 10.2. [Table 10]
[0194] As shown in Table 10, the composite membranes of Examples 10.1 and 10.2 have similar thicknesses (i.e., 8.8 and 10.3 microns, respectively) and similar total acid contents (i.e., 1.8 and 1.9 meq / cc, respectively). Thus, the composite membranes of Examples 10.1 and 10.2 have similar conductance characteristics as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that variations in the final mass of the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and ion exchange material (e.g., perfluorosulfonic acid resin) produced very different composite membrane permeance characteristics. For example, the composite membrane of Example 10.2 showed improved or increased selectivity compared to the composite membrane of Example 10.1 (i.e., 0.6 MPA / mV of Example 10.2 compared to 0.4 MPA / mV of Example 10.1 at 50% RH). The increase or improvement in selectivity is illustrated by line 320 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0195] Combining the data from Example Series 1-10, we show that adding more inert microporous polymer structure (ePTFE in this case) and keeping the total acid content of the membrane constant improves fuel cell performance for multilayer composite membranes in the thickness range of 4.9-14.5 microns or for multilayer composite membranes used in fuel cell applications, regardless of the type of microporous polymer used, whether one or more microporous polymers are present, which IEM is used, whether the IEM is made from a blend, or whether the composite membrane has the same IEM on both sides of the composite membrane's occluded microporous polymer structure. This is a surprising and unexpected finding.
[0196] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 10.2 compared to Example 10.1, the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Example 10.2 compared to Example 10.1 could be reduced, thereby increasing the total volume of the microporous polymer structure from 3% in Example 10.1 to 20.8% in Example 10.2, resulting in improved reinforcement of the composite membrane and reduced manufacturing costs of the composite membrane (i.e., reduced final mass of expensive ion exchange material used to manufacture the composite membrane).
[0197] Series 11 Comparative Example 11.1 Comparative Example 11.1 was prepared by the following procedure. The mass per area was 0.6 g / m 2Two sheets of ePTFE membrane 1, 3.6 μm thick, 0.17 g / cc apparent density, and 75.0 psi bubble point, were manually stretched to remove wrinkles and restrained in this state in a metal frame. A first laydown of EV=509 cc / mol equivalent of PSFA solution (D2020 obtained from Ion Power Inc., USA), 22.1% water, 62.9% ethanol, 15% solids solution composition as IEM was then coated on the top surface of the polymer sheet substrate. The polymer sheet substrate (obtained from DAICEL VALUE COATING LTD., Japan) contained a protective layer of PET and cyclic olefin copolymer (COC) and was oriented with the COC side facing up. The IEM (PFSA solution) coating was obtained using a Meyer bar with a nominal wet coating thickness of 2.2 mils. While the coating was still wet, a first ePTFE membrane 1, previously restrained on a metal frame, was laminated to the coating, during which the IEM solution was absorbed into the pores. The composite was then dried in a convection oven with internal air at a temperature of 165°C. Upon drying, the microporous polymer structure (ePTFE membrane) was fully absorbed into the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer sheet substrate. In the second laydown, the same solution of IEM was coated on the top surface of the composite (opposite surface of the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 3 mils. While the coating was still wet, a second ePTFE membrane 1, previously restrained on a metal frame, was laminated to the coating, during which the IEM solution was absorbed into the pores. The composite was then dried again at 165°C. Upon drying, the second microporous polymer structure (ePTFE membrane) was fully absorbed into the second laydown of IEM. In the second laydown, the IEM was also layered between two layers of microporous polymer substrate. In the third laydown, the same solution of IEM was coated onto the top surface of the composite (the surface opposite the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 2 mils. The composite was then dried again at 165°C, at which point it was nearly transparent, indicating complete impregnation of the microporous polymer structure.The multi-layer composite membrane was completely occlusive, with a layer of IEM between two completely occlusive microporous polymer layers on each side. The resulting multi-layer composite membrane had a thickness of 11.4 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 4.7 vol.%, and an acid content of 1.9 meq / cc. The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 11.
[0198] Invention Example 11.2 Inventive Example 11.2 was prepared by the same procedure as above and that used for Comparative Example 11.1, except that different materials were used. 2A first ePTFE membrane 4 with a thickness of 9.6 μm, an apparent density of 0.29 g / cc, and a bubble point of 34.4 psi was used as the microporous polymer structure. A solution composition of PSFA solution (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China) as IEM with EV=413 cc / molar equivalent, 17.3% water, 71.5% ethanol, and 11.2% solids was used to coat in the first laydown using a drawdown bar with a nominal wet coating thickness of 3 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 4 mils. While the coating was still wet, a second ePTFE membrane 4 pre-restrained on a metal frame was laminated to the coating, during which the IEM solution was absorbed into the pores. In the third laydown, a solution of PSFA as IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China) with EV=413 cc / molar equivalent, 6.2% water, 89.8% ethanol, 4.0% solids was coated on the top surface of the composite (opposite surface of the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 3 mils. The multilayer composite membrane was completely occlusive, with a layer of IEM between two completely occlusive microporous polymer layers on both sides. The resulting composite membrane had a thickness of 9.4 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 26.4 vol.%, and an acid content of 1.8 meq / cc. The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 11.
[0199] Table 11 shows the results of various test procedures for the composites of Comparative Example 11.1 and Inventive Example 11.2. [Table 11]
[0200] As shown in Table 11, the composite membranes of Examples 11.1 and 11.2 have similar thicknesses (i.e., 11.4 and 9.4 microns, respectively) and similar total acid contents (i.e., 1.9 and 1.8 meq / cc, respectively). Thus, the composite membranes of Examples 11.1 and 11.2 have similar conductance characteristics as demonstrated by resistivity measurements. However, it has been surprisingly and unexpectedly discovered that variations in the final mass of the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and ion exchange material (e.g., perfluorosulfonic acid resin) produce very different composite membrane permeance characteristics. For example, the composite membrane of Example 11.2 shows improved or increased selectivity compared to the composite membrane of Example 11.1 (i.e., 0.5 MPA / mV of Example 11.2 compared to 0.4 MPA / mV of Example 11.1 at 50% RH). The increase or improvement in selectivity is illustrated by line 322 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0201] Combining the data from Example Series 1-11, we show that adding more inert microporous polymer structure (ePTFE in this case) and keeping the total acid content of the membrane constant improves the fuel cell performance of multilayer composite membranes in the thickness range of 4.9-14.5 microns or multilayer composite membranes used in fuel cell applications, regardless of the type of microporous polymer used, or whether there is more than one microporous polymer, or whether multiple occluded microporous polymer layers are in contact or separated by a layer of IEM, or which IEM is used, or whether the IEM is made from a blend, or whether the composite membrane has the same IEM on both sides of the occluded microporous polymer structure. This is a surprising and unexpected finding.
[0202] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 11.2 compared to Example 11.1, it was possible to lower the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Example 11.2 compared to Example 11.1, thereby increasing the total volume of the microporous polymer structure from 4.7% in Example 11.1 to 26.4% in Example 11.2, resulting in improved reinforcement of the composite membrane (and reduced manufacturing costs of the composite membrane (i.e., reduced final mass of expensive ion exchange material used to manufacture the composite membrane)).
[0203] Series 12 Comparative Example 12.1 Comparative Example 12.1 was prepared by the same procedure used in Comparative Example 1.1, except that a different material was used: a mass per area of 0.6 g / m 2 ePTFE membrane 1, with a thickness of 3.6 μm, an apparent density of 0.17 g / cc, and a bubble point of 75.0 psi, was used as the microporous polymer matrix. A solution of IEM (D2020 obtained from Ion Power Inc., USA) with EV=509 cc / molar equivalent, 22.1% water, 62.9% ethanol, and 15% solids composition was coated in the first laydown using a Mayer bar with a nominal wet coating thickness of 0.6 mils. In the second laydown, the same solution of IEM was coated on the top surface of the composite (the surface opposite the substrate) using a drawdown bar with a nominal wet coating thickness of 0.5 mils. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix. The resulting multilayer composite membrane had a thickness of 2.2 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 11.9 vol.%, and an acid content of 1.7 meq / cc.
[0204] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 12.
[0205] Invention Example 12.2 Inventive Example 12.2 was prepared by the same procedure used for Comparative Example 10.1, except that different materials were used: a mass per area of 1.2 g / m2 ePTFE membrane 3 with a thickness of 5.4 μm, an apparent density of 0.23 g / cc, and a bubble point of 38.0 psi was used as the microporous polymer matrix. A solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 13.0% water, 74.7% ethanol, and 12.3% solids, with an EV=458 cc / molar equivalent, was coated in the first laydown using a Mayer bar with a nominal wet coating thickness of 0.9 mils. In the second laydown, a solution of IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 5.5% water, 94.0% ethanol, and 0.5% solids, with an EV=413 cc / molar equivalent, was coated on the top surface (the surface opposite the substrate) of the composite using a drawdown bar with a nominal wet coating thickness of 5 mils. The multi-layer composite membrane was completely occlusive, with a layer of IEM on each side of the microporous polymer matrix. The resulting multi-layer composite membrane had a thickness of 2.5 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 21.2 vol.%, and an acid content of 1.8 meq / cc.
[0206] Table 12 shows the results of various test procedures for the composites of Comparative Example 12.1 and Inventive Example 12.2. [Table 12]
[0207] As shown in Table 12, the composite membranes of Examples 12.1 and 12.2 have similar thicknesses (i.e., 2.2 and 2.5 microns, respectively) and similar total acid contents (i.e., 1.7 and 1.8 meq / cc, respectively). Thus, the composite membranes of Examples 12.1 and 12.2 have similar conductance characteristics as demonstrated by resistivity measurements. However, it has been surprisingly and unexpectedly discovered that variations in the final mass of the microporous polymer structure (e.g., expanded porous polytetrafluoroethylene) and ion exchange material (e.g., perfluorosulfonic acid resin) produce very different composite membrane permeance characteristics. For example, the composite membrane of Example 12.2 shows improved or increased selectivity compared to the composite membrane of Example 12.1 (i.e., 0.4 MPA / mV for Example 12.2 compared to 0.3 MPA / mV for Example 12.1 at 50% RH). The increase or improvement in selectivity is illustrated by line 324 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0208] Combining the data from Example Series 1-11, we show that adding more inert microporous polymer structure (ePTFE in this case) and keeping the total acid content of the membrane constant improves the fuel cell performance of multilayer composite membranes in the thickness range of 2.5-14.5 microns or multilayer composite membranes used in fuel cell applications, regardless of the type of microporous polymer used, or whether there is more than one microporous polymer, or whether multiple occluded microporous polymer layers are in contact or separated by a layer of IEM, or which IEM is used, or whether the IEM is made from a blend, or whether the composite membrane has the same IEM on both sides of the occluded microporous polymer structure. This is a surprising and unexpected finding.
[0209] Additionally, by increasing the final mass of the microporous polymer structure (e.g., ePTFE) in Example 12.2 compared to Example 12.1, it was possible to lower the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) in Example 12.2 compared to Example 12.1, thereby increasing the total volume of the microporous polymer structure from 11.9% in Example 12.1 to 21.20% in Example 12.2, resulting in improved reinforcement of the composite membrane and reduced manufacturing costs of the composite membrane (i.e., reduced final mass of expensive ion exchange material used to manufacture the composite membrane).
[0210] Series 13 Series 13 includes only two comparative examples and is unreinforced. Thus, the composite membranes of Comparative Examples 13.1 and 13.2 do not contain a microporous polymer structure. The composite membrane used in Example 13.1 is a non-reinforced Nafion® membrane 211 obtained from Ion Power Inc., USA. The composite membrane used in Example 13.2 is a non-reinforced Nafion® membrane 212 obtained from Ion Power Inc., USA.
[0211] Table 13 shows the results of various test procedures for the composites of Comparative Examples 13.1 and 13.2. [Table 13]
[0212] As shown in Table 13, the composite membranes of Examples 13.1 and 13.2 have the same total acid content (i.e., 1.8 meq / cc) and the same selectivity (i.e., 0.5 MPA / mV) even though they have different thicknesses (i.e., 23.9 and 47.7 microns, respectively). Table 13 further shows the proton conductance (resistance) and hydrogen permeance (i.e., H2 resistance) of the Nafion composite membranes. These membranes are commercially available and can be used as reference materials. The selectivity of Comparative Examples 13.1 and 13.2 is shown using data point 326 in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0213] Series 14 Comparative Example 14.1 Comparative Example 14.1 was prepared by the following procedure: The mass per area was 7.9 g / m 2A track-etched polycarbonate porous membrane 12 with a thickness of 9.3 μm, an apparent density of 85 g / cc, and a bubble point of 0.9 psi was obtained from Structure Probe, Inc., USA under part number E14047-MB. This porous membrane exhibited sufficient rigidity that it was not necessary to restrain the porous membrane on a metal frame. A first laydown of EV=413 cc / molar equivalent of PFSA solution as IEM (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 17.3% water, 71.5% ethanol, 11.2% solids solution composition was then coated on the top surface of the polymer sheet substrate. The polymer sheet substrate (obtained from DAICEL VALUE COATING LTD., Japan) contained a protective layer of PET and cyclic olefin copolymer (COC) and was oriented with the COC side facing up. The IEM (PFSA solution) coating was obtained using a drawdown bar with a nominal wet coating thickness of 1.5 mils. While the coating was still wet, a track-etched polycarbonate porous membrane 12 was laminated to the coating, during which the IEM solution was absorbed into the pores. The composite was then dried in a convection oven with internal air at a temperature of 95° C. Upon drying, the microporous polymer structure (the track-etched polycarbonate porous membrane) was completely absorbed with the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer sheet substrate. In a second laydown, the same solution of IEM was coated onto the top surface of the composite (the surface opposite the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 4 mils. The composite was then dried again at 95° C., at which point it was nearly transparent, indicating complete impregnation of the microporous polymer structure. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix, and these layers of IEM had unequal equivalent volumes. The resulting multi-layer composite membrane had a thickness of 12.3 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 53.4 vol. %, and an acid content of 1.1 meq / cc.
[0214] The results of the proton / hydrogen gas transport selectivity measurements are shown in Table 14.
[0215] Invention Example 14.2 Inventive Example 14.2 was prepared by the same procedure as described above in relation to Comparative Example 14.1, except that different materials were used: a mass per area of 10.37 g / m 2A track-etched polycarbonate porous membrane 13 with a thickness of 12.3 μm, an apparent density of 0.85 g / cc, and a bubble point of 1.1 psi was obtained from Structure Probe, Inc., USA under the number E20047-MB. This porous membrane exhibited sufficient rigidity that it was not necessary to restrain the porous membrane on a metal frame. A first laydown of a solution composition of PFSA solution as IEM with EV=311 cc / molar equivalent (obtained from Shanghai Gore 3F Fluoromaterials Co., LTD., China), 21.5% water, 65.5% ethanol, 13.0% solids was then coated on the top surface of the polymer sheet substrate. The polymer sheet substrate (obtained from DAICEL VALUE COATING LTD., Japan) contained a protective layer of PET and cyclic olefin copolymer (COC) and was oriented with the COC side facing up. The IEM (PFSA solution) coating was obtained using a drawdown bar with a nominal wet coating thickness of 1 mil. While the coating was still wet, a track-etched polycarbonate porous membrane 13 was laminated to the coating, resulting in the IEM solution being absorbed into the pores. The composite was subsequently dried in a convection oven with internal air at a temperature of 95°C. Upon drying, the microporous polymer structure (the track-etched polycarbonate porous membrane) was completely absorbed into the IEM. The IEM also formed a layer between the bottom surface of the microporous polymer substrate and the polymer sheet substrate. In a second laydown, the same solution of IEM was coated onto the top surface of the composite (the surface opposite the polymer sheet substrate) using a drawdown bar with a nominal wet coating thickness of 2 mils. The composite was then dried again at 95°C, at which point it was nearly transparent, indicating complete impregnation of the microporous polymer structure. The multilayer composite membrane was completely occlusive, with a layer of IEM on both sides of the microporous polymer matrix, and these layers of IEM had unequal equivalent volumes. The resulting multi-layer composite membrane had a thickness of 13.5 microns at 0% RH, a volume fraction occupied by the microporous polymer structure of 64.0% by volume, and an acid content of 1.2 meq / cc.
[0216] Table 14 shows the results of various test procedures for the composites of Comparative Example 14.1 and Inventive Example 14.2. [Table 14]
[0217] As shown in Table 14, the composite membranes of Examples 14.1 and 14.2 have similar thicknesses (i.e., 12.3 and 13.5 microns, respectively) and similar total acid contents (i.e., 1.1 and 1.2 meq / cc, respectively). Thus, the composite membranes of Examples 14.1 and 14.2 have similar conductance characteristics as demonstrated by resistivity measurements. However, it was surprisingly and unexpectedly discovered that variations in the microporous polymer structure (e.g., track-etched porous polycarbonate) and the final mass of the ion exchange material (e.g., perfluorosulfonic acid resin) produce very different permeance characteristics of the composite membranes. For example, the composite membrane of Example 14.2 showed improved or increased selectivity compared to that of the composite membrane of Example 14.1 (i.e., 0.094 MPA / mV for Example 14.2 compared to 0.081 MPA / mV for Example 14.1 at 50% RH). The increase or improvement in selectivity is illustrated by line 328 shown in graph 300 of FIG. 3A and graph 350 of FIG. 3B.
[0218] Combining the data from Example Series 1-14 shows that while keeping the total acid content of the membrane constant, adding more inert microporous polymer structures, such as perfluorinated ePTFE or hydrocarbon track etched porous polycarbonate, improves the fuel cell performance of multilayer composite membranes used in fuel cell applications, regardless of (a) thickness of the multilayer composite membrane ranging from 2.5 to 14.5 microns, (b) type of microporous polymer used, (c) whether one or more microporous polymers are present, (d) which IEMs are used, (e) whether the IEMs are made from a blend, or (f) whether the composite membrane has the same IEMs on both sides of the plugged microporous polymer structure. This is a surprising and unexpected finding.
[0219] Although the present invention has been described in detail, modifications within the spirit and scope of the present invention will be readily apparent to those skilled in the art. It will be understood that the aspects of the present invention and the various embodiments and portions of the various features recited above and / or in the appended claims may be combined or interchanged, either in whole or in part. In the above description of various embodiments, those embodiments that refer to other embodiments may be appropriately combined with other embodiments, as will be understood by those skilled in the art. Furthermore, those skilled in the art will understand that the above description is merely exemplary and is not intended to limit the present invention.
Claims
1. a) a microporous polymer structure present in an amount of 13% to 65% by volume based on the total volume of the composite polymer electrolyte membrane at 0% relative humidity; and b) an ion exchange material at least partially embedded within and occluding said microporous polymer structure; A composite polymer electrolyte membrane comprising: said microporous polymer structure having an average pore size of 0.01 to 100 microns; the thickness of the composite polymer electrolyte membrane is less than 17 microns at 0% relative humidity, the acid content of the composite polymer electrolyte membrane is between 1.2 meq / cc and 3.5 meq / cc at 0% relative humidity, and The composite polymer electrolyte membrane has a selectivity, which is the ratio of conductance to permeance at a relative humidity of 50%, of greater than 0.05 MPa / mV.
2. 2. The composite polymer electrolyte membrane of claim 1, wherein said ion exchange material has an equivalent volume of less than or equal to 460 cc / mole equivalents, where said equivalent volume is the ratio of the equivalent weight of said ion exchange material divided by the volumetric density of said ion exchange material at 0% relative humidity.
3. 3. The composite polymer electrolyte membrane according to claim 1, wherein the ion exchange material is a perfluorinated ion exchange material.
4. 3. The composite polymer electrolyte membrane of claim 1 or 2, wherein the ion exchange material is selected from the group consisting of perfluorosulfonic acid polymers, perfluorocarboxylic acid polymers, perfluorophosphonic acid polymers, styrene-based ion exchange polymers, fluorostyrene ion exchange polymers, polyaryletherketone ion exchange polymers, polysulfone ion exchange polymers, bis(fluoroalkylsulfonyl)imides, (fluoroalkylsulfonyl)(fluorosulfonyl)imides, polyvinyl alcohol, polyethylene oxide, divinylbenzene, metal salts with or without polymers, and mixtures thereof.
5. 3. A method of forming a composite polymer electrolyte membrane according to claim 1 or 2, wherein the microporous polymer structure is completely impregnated with an ion exchange material, and wherein the composite polymer electrolyte membrane further comprises two additional layers of ion exchange material, comprising: Provide a support structure; applying a first ionomer solution comprising an ion exchange material dissolved in a solvent to the support structure in a layer of controlled thickness in a single or multiple pass ionomer coating technique; laminating an untreated microporous polymer structure onto at least a portion of the first ionomer solution to provide a treated microporous polymer structure; drying the treated microporous polymer structure to provide a dry composite material having the ion exchange material affixed to an interior membrane surface of the microporous polymer structure; applying a second ionomer solution comprising an ion exchange material dissolved in a solvent onto the dried composite material in a layer of controlled thickness in a single or multiple pass ionomer coating technique to provide a second ionomer solution coated structure; and drying the second ionomer solution coated structure to provide a composite polymer electrolyte membrane.
6. The support structure comprises: a scrim made of woven fibers of expanded porous polytetrafluoroethylene, a web made of extruded or oriented polypropylene or polypropylene netting, and a woven material selected from woven materials of polypropylene and polyester; a nonwoven material selected from spunbond polypropylene; or Polyethylene (PE), polystyrene (PS), cyclic olefin copolymer (COC), cyclic olefin polymer (COP), fluorinated ethylene propylene (FEP), perfluoroalkoxyalkane (PFA), ethylene tetrafluoroethylene (ETFE), polyvinylidene fluoride (PVDF), polyetherimide (PEI), polysulfone (PSU), polyethersulfone (PES), polyphenylene oxide (PPO), polyphenylether (PPE), polymethylpentene (PMP), polyethylene terephthalate (PET) or polycarbonate (PC) webs The method according to claim 5, wherein
7. 6. The method of claim 5, wherein the support structure further comprises a protective layer selected from polyethylene (PE), polystyrene (PS), cyclic olefin copolymer (COC), cyclic olefin polymer (COP), fluorinated ethylene propylene (FEP), perfluoroalkoxyalkane (PFA), ethylene tetrafluoroethylene (ETFE), polyvinylidene fluoride (PVDF), polyetherimide (PEI), polysulfone (PSU), polyethersulfone (PES), polyphenylene oxide (PPO), polyphenylether (PPE), polymethylpentene (PMP), polyethylene terephthalate (PET), or polycarbonate (PC).
8. The method of claim 5 , wherein the support structure further comprises a reflective layer comprising a metal substrate.
9. 6. The method of claim 5, wherein the single pass or multi-pass ionomer coating technique is selected from forward roll coating, reverse roll coating, gravure coating, doctor coating, kiss coating, slot die coating, slide die coating, dipping, brushing, painting and spraying.
10. 6. The method of claim 5, wherein said drying comprises heating in an oven at a temperature greater than 60°C.
11. the second ionomer solution is the same as the first ionomer solution, or The method of claim 5 , wherein the second ionomer solution is different from the first ionomer solution.
12. The mass per unit area of the composite polymer electrolyte membrane is 0.2 g / m at 0% relative humidity. 2 The method of claim 5 , wherein
13. The method of claim 5, wherein the ion exchange material is a perfluorinated ion exchange material.
14. 3. A method of forming a composite polymer electrolyte membrane according to claim 1 or 2, in which two microporous polymer structures are in contact with each other and are completely impregnated with an ion exchange material, the composite polymer electrolyte membrane further comprising two additional layers of ion exchange material, the method comprising the steps of: Provide a support structure; applying a first ionomer solution comprising an ion exchange material dissolved in a solvent to the support structure in a layer of controlled thickness in a single or multiple pass ionomer coating technique; laminating a first untreated microporous polymer structure over a portion of the first ionomer solution and a second untreated microporous polymer structure over the same portion of the first ionomer solution on the first untreated microporous polymer structure to provide a treated microporous polymer structure; drying the treated microporous polymer structure to provide a dry composite material having the ion exchange material affixed to an interior membrane surface of the microporous polymer structure; applying a second ionomer solution comprising an ion exchange material dissolved in a solvent onto the dried composite material in a layer of controlled thickness in a single or multiple pass ionomer coating technique to provide a coated structure coated with the second ionomer solution; and and drying the coated structure with the second ionomer solution to provide a composite polymer electrolyte membrane.
15. The method of claim 14 , wherein the first and second untreated microporous polymer structures comprise ePTFE having a microporous polymer structure.
16. the second untreated microporous polymer structure is the same as the first untreated microporous polymer structure, or The method of claim 14 , wherein the second untreated microporous polymer structure is different from the first untreated microporous polymer structure.
17. The method of claim 14, wherein the ion exchange material is a perfluorinated ion exchange material.
18. 3. A method of forming a composite polymer electrolyte membrane according to claim 1 or 2, comprising two microporous polymer structures each completely impregnated with an ion exchange material, the two microporous polymer structures being separated from each other by a layer of ion exchange material, the composite polymer electrolyte membrane further comprising: Provide a support structure; applying a first ionomer solution comprising an ion exchange material dissolved in a solvent to the support structure in a layer of controlled thickness in a single or multiple pass ionomer coating technique; laminating a first untreated microporous polymer structure onto at least a portion of the first ionomer solution to provide a first treated microporous polymer structure; drying the treated first microporous polymer structure to provide a first dry composite material having the ion exchange material affixed to an interior membrane surface of the microporous polymer structure; applying a second ionomer solution comprising an ion exchange material dissolved in a solvent onto the first dried composite material in a layer of controlled thickness in a single or multiple pass ionomer coating technique; laminating a second untreated microporous polymer structure over at least a portion of the second ionomer solution to provide a second treated microporous polymer structure; drying the treated second microporous polymer structure to provide a second dry composite material having the ion exchange material affixed to an interior membrane surface of the microporous polymer structure; providing a third treated microporous polymer structure by applying a third ionomer solution comprising an ion exchange material dissolved in a solvent as a layer of controlled thickness over the second dried composite material in a single or multiple pass ionomer coating technique; and drying the third treated microporous polymer structure to provide a composite polymer electrolyte membrane.
19. The method of claim 18 , wherein the second untreated microporous polymer structure comprises ePTFE having a microporous polymer structure.
20. the second untreated microporous polymer structure is the same as the first untreated microporous polymer structure, or The method of claim 18 , wherein the second untreated microporous polymer structure is different from the first untreated microporous polymer structure.
21. the third ionomer solution is the same as the first and / or second ionomer solution, or 20. The method of claim 18, wherein the third ionomer solution is different from the first and / or second ionomer solutions.
22. 20. The method of claim 18, wherein the ion exchange material is a perfluorinated ion exchange material.
Citation Information
Patent Citations
Composite membrane consisting of partial elements
JP1999501964A
Fluorine-based polymer electrolyte film
JP2014110232A
